Polymerizable composition for optical material, polymerizable prepolymer composition for optical material, cured product, and method for producing optical material
By using a polymerizable composition containing a variety of monomers for optical materials and a polymerization catalyst, the problems of long manufacturing time and poor quality of optical materials are solved, and the effect of shortening the manufacturing time and improving quality is achieved.
Patent Information
- Application Number
- CN202510054691.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2020-11-24
- Filing Date
- 2021-03-10
- Publication Date
- 2025-04-22
AI Technical Summary
The prior art when manufacturing optical materials, the time is long and economical cost is high, and shortening the heating polymerization time will lead to insufficient polymerization, resulting in poor conditions such as non-curing of the optical materials or generating ribs, which will affect quality.
The polymerizable composition containing two or more monomers for different optical materials and a polymerization catalyst is used to adjust the content and viscosity of the polymerization catalyst to promote polymerization reaction, shorten the manufacturing time, and prevent the generation of ribs.
It effectively shortens the manufacturing time of optical materials, maintains the quality of optical materials, avoids the generation of ribs, and improves working efficiency and economic costs.
Smart Images

Figure CN119859267A_ABST
Abstract
Description
[0001] This application is a divisional application of Chinese invention patent application No. 202180018632.9 (PCT application number is PCT / JP2021 / 009611), whose application date is March 10, 2021 and whose invention name is "Polymerizable composition for optical materials, polymerizable prepolymer composition for optical materials, cured product and method for manufacturing optical material". Technical Field
[0002] The present disclosure relates to a polymerizable composition for an optical material, a polymerizable prepolymer composition for an optical material, a cured product, and a method for producing an optical material. Background Art
[0003] Examples of a method for producing a resin that can be used in an optical material for a plastic lens include a cast polymerization method in which a polymerizable composition containing a monomer is injected into a mold (casting mold) and then cured by heating.
[0004] In the casting polymerization method, after preparing a polymerizable composition and degassing it, the polymerizable composition is injected into a mold (casting mold), cured by heating (polymerization reaction), and the product is taken out of the mold (demolding) and annealed to obtain an optical material (for example, a lens, a semi-finished blank, etc.).
[0005] In order to improve the quality of optical materials, heat curing is usually carried out by slowly raising the temperature through heating while performing polymerization reaction over several hours to tens of hours, specifically, usually requiring about 20 hours to 48 hours. In addition, it is known that a lot of the total time of the manufacturing process (for example, 90% of the total time) is consumed in the time used for polymerization.
[0006] In the examples of Patent Document 1, it is described that a mold into which a polymerizable composition is injected is gradually heated from 10° C. to 120° C., and polymerization is performed over 20 hours to obtain a molded body.
[0007] In addition, in the examples of Patent Document 2, it is described that the mold into which the polymerizable composition was injected was gradually heated from 25° C. to 120° C. over 16 hours, and heated at 120° C. for 4 hours to obtain a molded body.
[0008] Patent Document 1: International Publication No. 2014 / 027427
[0009] Patent Document 2: International Publication No. 2014 / 133111 Summary of the invention
[0010] Problems to be solved by the invention
[0011] As described above, conventionally, in the process of producing an optical material, the polymerization reaction is generally carried out over several hours to several tens of hours (for example, about 20 hours to 48 hours) while gradually raising the temperature by heating.
[0012] However, since the production of optical materials takes a long time, it is necessary to operate the equipment involved in the production for a long time, which imposes a large economic burden and impairs the work efficiency.
[0013] On the other hand, when optical materials are manufactured using conventional methods, if the heating polymerization time is shortened to carry out the polymerization reaction, the polymerization will be insufficient, which will result in the optical material not being cured, or even if it is cured, undesirable conditions such as wave lines will occur in the optical material, and the quality of the optical material may be reduced.
[0014] Based on the above, in the production of optical materials, it is required to maintain the quality of the obtained optical materials and to shorten the production time of the optical materials.
[0015] An object of one embodiment of the present disclosure is to provide a method for producing an optical material that can maintain the quality of the obtained optical material and shorten the production time of the optical material.
[0016] Another problem to be solved by one embodiment of the present disclosure is to provide a polymerizable composition for an optical material that can be used in a method for producing an optical material, which can maintain the quality of the obtained optical material and shorten the production time of the optical material.
[0017] Means for solving problems
[0018] Specific means for solving the above-mentioned problems include the following aspects.
[0019] The first embodiment of the present disclosure includes the following aspects.
[0020] <1> A polymerizable composition for an optical material, comprising two or more different monomers for an optical material, and a polymerization catalyst, wherein the content of the polymerization catalyst relative to the total amount of the monomers for an optical material is 0.1150 to 0.2000 parts by mass, the polymerizable composition for an optical material having a viscosity of 10 to 1000 mPa·s as measured using a Brookfield viscometer at 20° C. and 60 rpm, and at least one of the two or more different monomers for an optical material is an episulfide compound.
[0021] <2> The polymerizable composition for an optical material according to <1>, wherein the thixotropic ratio is 1.3 or less.
[0022] <3> The polymerizable composition for an optical material as described in <1> or <2>, comprising two or more different monomers for an optical material, a polymerization catalyst, and a prepolymer having a polymerizable functional group, wherein the prepolymer having a polymerizable functional group is a polymer of the two or more different monomers for an optical material, and at least one of the two or more different monomers for an optical material is an episulfide compound.
[0023] <4> The polymerizable composition for an optical material according to any one of <1> to <3>, wherein the two or more different monomers for an optical material include at least one selected from the group consisting of polythiol compounds, polyol compounds, isocyanate compounds, and amine compounds.
[0024] <4-1> The polymerizable composition for an optical material according to any one of <1> to <4>, wherein the polymerization catalyst satisfies the following condition 1.
[0025] [Condition 1]
[0026] -Ea / R is above -7100 and below -1500.
[0027] (Ea is the activation energy calculated from the reaction rate constants of the two or more different monomers for optical materials at two or more different temperatures using an Arrhenius plot, and R is the gas constant (8.314 J / mol / K).)
[0028] <5> The polymerizable composition for an optical material according to any one of <1> to <4-1>, wherein the polymerization catalyst comprises at least one selected from the group consisting of a basic catalyst having a pKa value of 5 to 12 and an organometallic catalyst.
[0029] <5-1> The polymerizable composition for an optical material according to any one of <1> to <5>, wherein the polymerization catalyst comprises at least one selected from the group consisting of amine catalysts and organotin catalysts.
[0030] <5-2> The polymerizable composition for an optical material as described in any one of <1> to <5-1>, wherein the polymerization catalyst comprises at least one selected from the group consisting of N,N-dimethylcyclohexylamine, N,N-dicyclohexylmethylamine, 3,5-lutidine, 2,4,6-trimethylpyridine, triethylenediamine, N,N-dimethylethanolamine, N-ethylmorpholine, dibutyltin dichloride, dimethyltin dichloride, dibutyltin dilaurate and dibutyltin diacetate.
[0031] <6> A polymerizable prepolymer composition for an optical material, comprising a prepolymer having a polymerizable functional group and a polymerization catalyst, wherein the prepolymer having a polymerizable functional group is a polymer of two or more different monomers for an optical material, at least one of the two or more different monomers for an optical material is an episulfide compound, and the viscosity of the polymerizable prepolymer composition for an optical material, as measured by a Brookfield viscometer at 20° C. and 60 rpm, is 10 to 1000 mPa·s.
[0032] <7> The polymerizable prepolymer composition for an optical material according to <6>, wherein the content of the polymerization catalyst is 0.01 to 0.2 parts by mass based on 100 parts by mass of the total prepolymer.
[0033] <7-1> The polymerizable prepolymer composition for an optical material according to <6> or <7>, wherein the thixotropic ratio is 1.3 or less.
[0034] <8> The polymerizable prepolymer composition for an optical material according to any one of <6> to <7-1>, wherein the two or more different monomers for an optical material include at least one selected from the group consisting of a polythiol compound, a polyol compound, an isocyanate compound, and an amine compound.
[0035] <8-1> The polymerizable prepolymer composition for an optical material according to any one of <6> to <8>, wherein the polymerization catalyst satisfies the following condition 1.
[0036] [Condition 1]
[0037] -Ea / R is above -7100 and below -1500.
[0038] (Ea is the activation energy calculated from the reaction rate constants of the two or more different monomers for optical materials at two or more different temperatures using an Arrhenius plot, and R is the gas constant (8.314 J / mol / K).)
[0039] <9> The polymerizable prepolymer composition for an optical material according to any one of <6> to <8-1>, wherein the polymerization catalyst comprises at least one selected from the group consisting of a basic catalyst having a pKa value of 5 to 12 and an organic metal catalyst.
[0040] <9-1> The polymerizable prepolymer composition for an optical material according to any one of <6> to <9>, wherein the polymerization catalyst comprises at least one selected from the group consisting of amine catalysts and organotin catalysts.
[0041] <9-2> A polymerizable prepolymer composition for an optical material as described in any one of <6> to <9-1>, wherein the value obtained by subtracting the refractive index B of the prepolymer raw material composition from the refractive index A of the polymerizable prepolymer composition for an optical material is greater than 0, and the prepolymer raw material composition is a composition before forming the aforementioned prepolymer and comprises the aforementioned two or more different monomers for optical materials and a polymerization catalyst.
[0042] <10> A cured product of the polymerizable composition for an optical material according to any one of <1> to <5-2> or the polymerizable prepolymer composition for an optical material according to any one of <6> to <9-2>.
[0043] <10-1> The cured product as described in <10>, which is a cured product of the aforementioned polymerizable composition for optical material, wherein the aforementioned two or more different monomers for optical material include at least one selected from the group consisting of polythiol compounds, polyol compounds, isocyanate compounds, and amine compounds.
[0044] <10-2> The cured product according to <10> or <10-1>, which is a cured product of the polymerizable composition for an optical material, wherein the polymerization catalyst in the polymerizable composition for an optical material satisfies the following condition 1.
[0045] [Condition 1]
[0046] -Ea / R is above -7100 and below -1500.
[0047] (Ea is the activation energy calculated from the reaction rate constants of the two or more different monomers for optical materials at two or more different temperatures using an Arrhenius plot, and R is the gas constant (8.314 J / mol / K).)
[0048] <10-3> The cured product as described in any one of <10> to <10-2>, which is a cured product of the aforementioned polymerizable composition for optical material, wherein the aforementioned polymerization catalyst comprises at least one selected from the group consisting of a basic catalyst having a pKa value of 5 to 12 and an organic metal catalyst.
[0049] <10-4> The cured product according to any one of <10> to <10-3>, which is a cured product of the polymerizable composition for an optical material, wherein the polymerization catalyst in the polymerizable composition for an optical material comprises at least one selected from the group consisting of an amine catalyst and an organotin catalyst.
[0050] <10-5> The cured product as described in any one of <10> to <10-4>, which is a cured product of the aforementioned polymerizable composition for optical material, wherein the aforementioned polymerization catalyst comprises at least one selected from the group consisting of N,N-dimethylcyclohexylamine, N,N-dicyclohexylmethylamine, 3,5-lutidine, 2,4,6-trimethylpyridine, triethylenediamine, N,N-dimethylethanolamine, N-ethylmorpholine, dibutyltin dichloride, dimethyltin dichloride, dibutyltin dilaurate and dibutyltin diacetate.
[0051] <11> A method for producing an optical material, comprising the following steps: a preparation step of preparing a polymerizable composition for an optical material, the polymerizable composition for an optical material comprising two or more different monomers for an optical material, and a polymerization catalyst, at least one of the two or more different monomers for an optical material being an episulfide compound, and a content of the polymerization catalyst relative to the total amount of the two or more different monomers for an optical material being 0.1150 to 0.2000 parts by mass; a casting step of adjusting the viscosity of the polymerizable composition for an optical material to 10 to 1000 mPa·s as measured by a B-type viscometer at 20° C. and 60 rpm, and casting the composition into a mold; and a curing step of curing the polymerizable composition for an optical material by polymerizing the two or more different monomers for an optical material in the polymerizable composition for an optical material in the mold.
[0052] <12> A method for producing an optical material, comprising: a preparation step of preparing two or more different monomers for an optical material and a polymerization catalyst in an amount of 0.1150 to 0.2000 parts by mass based on the total amount of the two or more different monomers for an optical material; and a prepolymerization step of mixing at least a part of the two or more different monomers for an optical material and at least a part of the polymerization catalyst to polymerize at least a part of the two or more different monomers for an optical material to obtain a prepolymer, thereby obtaining a mixture containing the prepolymer, wherein at least one of the two or more different monomers for an optical material is an episulfide compound.
[0053] <13> The method for producing an optical material as described in <12>, which also includes the following steps: a step of producing a polymerizable composition for an optical material, comprising adding the remaining portion of the aforementioned polymerization catalyst, or a mixed solution of the remaining portion of the aforementioned two or more different monomers for an optical material and the remaining portion of the aforementioned polymerization catalyst to a mixture containing the aforementioned prepolymer, thereby obtaining a polymerizable composition for an optical material containing the aforementioned two or more different monomers for an optical material, the aforementioned prepolymer, and the aforementioned polymerization catalyst; and a curing step, wherein the aforementioned two or more different monomers for an optical material in the aforementioned polymerizable composition for an optical material are cured, thereby obtaining an optical material which is a cured product of the aforementioned polymerizable composition for an optical material.
[0054] <14> The method for producing an optical material according to any one of <11> to <13>, wherein the two or more different monomers for an optical material include at least one selected from the group consisting of a polythiol compound, a polyol compound, an isocyanate compound, and an amine compound.
[0055] <14-1> The method for producing an optical material according to any one of <11> to <14>, wherein the polymerization catalyst satisfies the following condition 1.
[0056] [Condition 1]
[0057] -Ea / R is above -7100 and below -1500.
[0058] (Ea is the activation energy calculated from the reaction rate constants of the two or more different monomers for optical materials at two or more different temperatures using an Arrhenius plot, and R is the gas constant (8.314 J / mol / K).)
[0059] <15> The method for producing an optical material according to any one of <11> to <14-1>, wherein the polymerization catalyst comprises at least one selected from the group consisting of a basic catalyst having a pKa value of 5 to 12 and an organic metal catalyst.
[0060] <16> The method for producing an optical material according to any one of <11> to <15>, wherein the polymerization catalyst includes at least one selected from the group consisting of amine catalysts and organotin catalysts.
[0061] <17> A cured product, which is a cured product of two or more different monomers for optical use, at least one of the two or more different monomers for optical materials being an episulfide compound, wherein no ribs having a length of 1.0 mm or more are present within a radius of 15 mm from the center of the cured product, and the amine content as measured by gas chromatography-mass spectrometry is from 0.01 mass % to 0.20 mass %.
[0062] This application relates to the following items:
[0063] Item 1. A polymerizable composition for an optical material, comprising two or more different monomers for an optical material, and a polymerization catalyst,
[0064] The content of the polymerization catalyst relative to the total amount of the monomer for optical material is 0.1150 to 0.2000 parts by mass,
[0065] The polymerizable composition for optical material has a viscosity of 10 mPa·s to 1000 mPa·s as measured by a B-type viscometer at 20° C. and 60 rpm.
[0066] At least one of the two or more different monomers for an optical material is an episulfide compound.
[0067] Item 2. The polymerizable composition for an optical material according to Item 1, wherein the thixotropic ratio is 1.3 or less.
[0068] Item 3. The polymerizable composition for an optical material according to Item 1 or 2, comprising:
[0069] The two or more different monomers for optical materials;
[0070] said polymerization catalyst; and
[0071] a prepolymer having a polymerizable functional group, wherein the prepolymer having a polymerizable functional group is a polymer of the two or more different monomers for optical materials,
[0072] At least one of the two or more different monomers for an optical material is an episulfide compound.
[0073] Item 4. The polymerizable composition for an optical material according to any one of Items 1 to 3, wherein the two or more different monomers for an optical material include at least one selected from the group consisting of polythiol compounds, polyol compounds, isocyanate compounds, and amine compounds.
[0074] Item 5. The polymerizable composition for an optical material according to any one of Items 1 to 4, wherein the polymerization catalyst comprises at least one selected from the group consisting of a basic catalyst having a pKa value of 5 to 12 and an organic metal catalyst.
[0075] Item 6. A polymerizable prepolymer composition for an optical material, comprising a prepolymer having a polymerizable functional group and a polymerization catalyst, wherein the prepolymer having a polymerizable functional group is a polymer of two or more different monomers for an optical material.
[0076] At least one of the two or more different monomers for optical materials is an episulfide compound,
[0077] The viscosity of the polymerizable prepolymer composition for an optical material measured by a B-type viscometer at 20° C. and 60 rpm is 10 mPa·s to 1000 mPa·s.
[0078] Item 7. The polymerizable prepolymer composition for an optical material according to Item 6, wherein the content of the polymerization catalyst is 0.01 to 0.2 parts by mass based on 100 parts by mass of the total prepolymer.
[0079] Item 8. The polymerizable prepolymer composition for an optical material according to Item 6 or 7, wherein the two or more different monomers for an optical material include at least one selected from the group consisting of a polythiol compound, a polyol compound, an isocyanate compound, and an amine compound.
[0080] Item 9. The polymerizable prepolymer composition for an optical material according to any one of Items 6 to 8, wherein the polymerization catalyst comprises at least one selected from the group consisting of a basic catalyst having a pKa value of 5 to 12 and an organic metal catalyst.
[0081] Item 10. A cured product of the polymerizable composition for an optical material according to any one of Items 1 to 5 or the polymerizable prepolymer composition for an optical material according to any one of Items 6 to 9.
[0082] Item 11. A method for producing an optical material, comprising the following steps:
[0083] a preparation step of preparing a polymerizable composition for an optical material, wherein the polymerizable composition for an optical material comprises two or more different monomers for an optical material and a polymerization catalyst,
[0084] At least one of the two or more different monomers for optical materials is an episulfide compound,
[0085] The content of the polymerization catalyst relative to the total amount of the two or more different monomers for optical materials is 0.1150 to 0.2000 parts by mass;
[0086] A casting step of adjusting the viscosity of the polymerizable composition for an optical material to 10 mPa·s to 1000 mPa·s as measured by a B-type viscometer at 20° C. and 60 rpm, and casting the composition into a mold; and
[0087] The curing step is to cure the polymerizable composition for optical material by polymerizing the two or more different monomers for optical material in the polymerizable composition for optical material in the mold.
[0088] Item 12. A method for producing an optical material, comprising the following steps:
[0089] a preparation step of preparing two or more different monomers for optical materials and a polymerization catalyst in an amount of 0.1150 to 0.2000 parts by mass based on the total amount of the two or more different monomers for optical materials; and
[0090] a prepolymerization step of mixing at least a part of the two or more different monomers for optical materials and at least a part of the polymerization catalyst, polymerizing at least a part of the two or more different monomers for optical materials to obtain a prepolymer, thereby obtaining a mixture containing the prepolymer;
[0091] At least one of the two or more different monomers for an optical material is an episulfide compound.
[0092] Item 13. The method for producing an optical material according to Item 12, further comprising the following steps:
[0093] a step of producing a polymerizable composition for an optical material, comprising adding the remaining portion of the polymerization catalyst, or a mixed solution of the remaining portion of the two or more different monomers for an optical material and the remaining portion of the polymerization catalyst to a mixture containing the prepolymer, thereby obtaining a polymerizable composition for an optical material containing the two or more different monomers for an optical material, the prepolymer, and the polymerization catalyst; and
[0094] The curing step is to obtain an optical material which is a cured product of the polymerizable composition for optical material by curing the two or more different monomers for optical material in the polymerizable composition for optical material.
[0095] Item 14. The method for producing an optical material according to any one of Items 11 to 13, wherein the two or more different monomers for an optical material include at least one selected from the group consisting of a polythiol compound, a polyol compound, an isocyanate compound, and an amine compound.
[0096] Item 15. The method for producing an optical material according to any one of Items 11 to 14, wherein the polymerization catalyst comprises at least one selected from the group consisting of a basic catalyst having a pKa value of 5 to 12 and an organic metal catalyst.
[0097] Item 16. The method for producing an optical material according to any one of Items 11 to 15, wherein the polymerization catalyst comprises at least one selected from the group consisting of amine catalysts and organotin catalysts.
[0098] Item 17. A cured product, which is a cured product of two or more different monomers for optical use, at least one of the two or more different monomers for optical materials is an episulfide compound, there are no ribs with a length of more than 1.0 mm within a radius of 15 mm from the center of the cured product, and the amine content measured by gas chromatography-mass spectrometry is more than 0.01 mass % and less than 0.20 mass %.
[0099] Effects of the Invention
[0100] According to one embodiment of the present disclosure, a method for producing an optical material can be provided that can maintain the quality of the obtained optical material and can effectively shorten the production time of the optical material.
[0101] According to another embodiment of the present disclosure, a polymerizable composition for an optical material that can be used in a method for producing an optical material can be provided, which can maintain the quality of the obtained optical material and can satisfactorily shorten the production time of the optical material. BRIEF DESCRIPTION OF THE DRAWINGS
[0102] [ Figure 1 ] is a graph showing the relationship between polymerization time and temperature when the total mass of the monomers for optical materials in the polymerizable composition for optical materials is 30 g and a molded body is manufactured using the polymerizable composition for optical materials of Example 1A, Example 2A to Example 4A, Example 5A and Example 6A. DETAILED DESCRIPTION
[0103] In the present disclosure, a numerical range expressed using "to" means a range including the numerical values described before and after "to" as the lower limit and the upper limit.
[0104] In the present disclosure, when a plurality of substances belonging to each component are present in a composition, unless otherwise specified, the amount of each component in the composition means the total amount of the plurality of substances present in the composition.
[0105] In the numerical ranges recorded in stages in this disclosure, the upper limit or lower limit recorded in one numerical range can be replaced by the upper limit or lower limit of the numerical range recorded in other stages. In addition, in the numerical ranges recorded in this disclosure, the upper limit or lower limit of the numerical range can be replaced by the value shown in the embodiments.
[0106] In the present disclosure, the term "process" refers not only to an independent process but also to a process that cannot be clearly distinguished from other processes as long as the intended purpose of the process can be achieved.
[0107] This disclosure includes a first embodiment and a second embodiment.
[0108] Each embodiment will be described.
[0109] -First Embodiment-
[0110] 《Polymerizable composition for optical materials》
[0111] The polymerizable composition for an optical material of the first embodiment comprises two or more different monomers for an optical material, and a polymerization catalyst, wherein the content of the polymerization catalyst relative to the total amount of the monomers for an optical material is 0.1150 to 0.2000 parts by mass, and the viscosity of the polymerizable composition for an optical material measured with a Brookfield viscometer at 20° C. and 60 rpm is 10 to 1000 mPa·s, and at least one of the two or more different monomers for an optical material is an episulfide compound.
[0112] The polymerizable composition for an optical material according to the first embodiment includes the above-mentioned configuration, thereby maintaining the quality of the obtained optical material and satisfactorily shortening the production time of the optical material.
[0113] (Monomers for optical materials)
[0114] The polymerizable composition for an optical material according to the first embodiment contains two or more different monomers for an optical material, and at least one of the two or more different monomers for an optical material is an episulfide compound.
[0115] By polymerizing the monomer for an optical material, strength and the like can be imparted to the optical material.
[0116] The monomer for optical material is not particularly limited as long as it is a monomer that can be used for optical applications.
[0117] For example, it may be a monomer that can be used to produce an optical material having any of the following properties.
[0118] The total light transmittance of the optical material obtained by using the monomer for optical material may be 10% or more. The total light transmittance of the optical material may be measured in accordance with JIS K 7361-1 (1997).
[0119] The haze (i.e., total haze) of the optical material obtained using the monomer for optical material may be 10% or less, preferably 1% or less, and more preferably 0.5% or less. The haze of the optical material is a value measured at 25° C. using a haze measuring machine [TC-HIIIDPK manufactured by Tokyo Denshoku Co., Ltd.] in accordance with JIS-K7105.
[0120] The refractive index of the optical material obtained using the optical material monomer is preferably 1.58 or more. The refractive index of the optical material obtained using the optical material monomer may be 1.80 or less, or 1.75 or less. The refractive index of the optical material may be measured according to JIS K7142 (2014).
[0121] The shape of the optical material obtained using the monomer for an optical material is not particularly limited, and may be a plate shape, a columnar shape, a rectangular parallelepiped shape, or the like.
[0122] (Episulfide compounds)
[0123] Examples of the episulfide compounds include epithioethylthio compounds, chain aliphatic 2,3-epithiopropylthio compounds, cyclic aliphatic 2,3-epithiopropylthio compounds, aromatic 2,3-epithiopropylthio compounds, chain aliphatic 2,3-epithiopropyloxy compounds, cyclic aliphatic 2,3-epithiopropyloxy compounds, aromatic 2,3-epithiopropyloxy compounds, and the like, and one or more of them may be used. Examples of these episulfide compounds include compounds exemplified in WO2015 / 137401.
[0124] In the first embodiment, from the viewpoint of maintaining the quality of the optical material and shortening the production time of the optical material, the episulfide compound is preferably at least one selected from the group consisting of bis(2,3-epithiopropyl)sulfide, bis(2,3-epithiopropyl)disulfide, bis(1,2-epithioethyl)sulfide, bis(1,2-epithioethyl)disulfide, and bis(2,3-epithiopropylthio)methane, and more preferably bis(2,3-epithiopropyl)disulfide.
[0125] The monomer for an optical material preferably further contains at least one of a polythiol compound and an isocyanate compound, and more preferably further contains a polythiol compound.
[0126] Examples of the monomer for an optical material include polymerizable monomers that are polymerized using a polymerization catalyst described later.
[0127] The two or more different monomers for an optical material preferably include at least one selected from the group consisting of a polythiol compound, a polyol compound, an isocyanate compound, and an amine compound.
[0128] (Polythiol Compounds)
[0129] The polythiol compound is a compound having two or more mercapto groups, and examples thereof include compounds exemplified in International Publication No. 2016 / 125736.
[0130] In the present disclosure, from the viewpoint of maintaining the quality of the optical material and shortening the production time of the optical material, the polythiol compound preferably comprises 4-mercaptomethyl-1,8-dimercapto-3,6-dithiaoctane, 5,7-dimercaptomethyl-1,11-dimercapto-3,6,9-trithiaundecane, 4,7-dimercaptomethyl-1,11-dimercapto-3,6,9-trithiaundecane, 4,8-dimercaptomethyl-1,11-dimercapto-3 , at least one of 6,9-trithiaundecane, pentaerythritol tetrakis(3-mercaptopropionate), bis(mercaptoethyl) sulfide, pentaerythritol tetrakis(2-mercaptoacetate), 2,5-bis(mercaptomethyl)-1,4-dithiacyclohexane, 1,1,3,3-tetrakis(mercaptomethylthio)propane, 4,6-bis(mercaptomethylthio)-1,3-dithiacyclohexane, and 2-(2,2-bis(mercaptomethylthio)ethyl)-1,3-dithiacyclohexane,
[0131] More preferably, it contains at least one selected from 4-mercaptomethyl-1,8-dimercapto-3,6-dithiaoctane, 5,7-dimercaptomethyl-1,11-dimercapto-3,6,9-trithiaundecane, 4,7-dimercaptomethyl-1,11-dimercapto-3,6,9-trithiaundecane, 4,8-dimercaptomethyl-1,11-dimercapto-3,6,9-trithiaundecane, pentaerythritol tetrakis(3-mercaptopropionate), and pentaerythritol tetrakis(2-mercaptoacetate),
[0132] It is further preferred that the compound contains at least one selected from 4-mercaptomethyl-1,8-dimercapto-3,6-dithiaoctane, 5,7-dimercaptomethyl-1,11-dimercapto-3,6,9-trithiaundecane, 4,7-dimercaptomethyl-1,11-dimercapto-3,6,9-trithiaundecane, 4,8-dimercaptomethyl-1,11-dimercapto-3,6,9-trithiaundecane, and pentaerythritol tetrakis(3-mercaptopropionate).
[0133] (Polyol Compound)
[0134] The polyol compound is a compound containing two or more hydroxyl groups, and one or more aliphatic or alicyclic alcohols can be mentioned. Specifically, linear or branched aliphatic alcohols, alicyclic alcohols, alcohols obtained by adding at least one selected from the group consisting of ethylene oxide, propylene oxide, and ε-caprolactone to these alcohols, etc. More specifically, the compounds exemplified in International Publication No. 2016 / 125736 can be mentioned.
[0135] The polyol compound is preferably at least one selected from ethylene glycol, diethylene glycol, triethylene glycol, propylene glycol, 1,3-propylene glycol, 1,2-cyclopentanediol, 1,3-cyclopentanediol, 1,2-cyclohexanediol, 1,3-cyclohexanediol, and 1,4-cyclohexanediol.
[0136] (Isocyanate compound)
[0137] As isocyanate compounds, aliphatic isocyanate compounds, alicyclic isocyanate compounds, aromatic isocyanate compounds, heterocyclic isocyanate compounds, etc. can be enumerated, and one or more of them can be used in a mixed manner. These isocyanate compounds can include dimers, trimers, and prepolymers. As these isocyanate compounds, the compounds exemplified in International Publication No. 2011 / 055540 can be enumerated.
[0138] It should be noted that in the present disclosure, an alicyclic isocyanate compound refers to an isocyanate compound that contains an alicyclic structure and may contain a heterocyclic structure. An aromatic isocyanate compound refers to an isocyanate compound that contains an aromatic structure and may contain an alicyclic structure and a heterocyclic structure. A heterocyclic isocyanate compound refers to an isocyanate compound that contains a heterocyclic structure and does not contain an alicyclic structure and an aromatic structure.
[0139] As the isocyanate compound, at least one selected from aliphatic isocyanate compounds, alicyclic isocyanate compounds, aromatic isocyanate compounds, and heterocyclic isocyanate compounds is preferably contained.
[0140] In the present disclosure, from the viewpoint of maintaining the quality of the optical material and shortening the production time of the optical material, the isocyanate compound preferably includes at least one selected from 2,5-bis(isocyanatemethyl)bicyclo-[2.2.1]-heptane, 2,6-bis(isocyanatemethyl)bicyclo-[2.2.1]-heptane, m-xylylene diisocyanate, 2,4-toluene diisocyanate, 2,6-toluene diisocyanate, dicyclohexylmethane diisocyanate, 1,3-bis(isocyanatemethyl)cyclohexane, 1,4-bis(isocyanatemethyl)cyclohexane, isophorone diisocyanate, 1,6-hexamethylene diisocyanate, and 1,5-pentamethylene diisocyanate.
[0141] More preferably, it contains at least one selected from 2,5-bis(isocyanatomethyl)bicyclo-[2.2.1]-heptane, 2,6-bis(isocyanatomethyl)bicyclo-[2.2.1]-heptane, m-xylylene diisocyanate, and 1,3-bis(isocyanatomethyl)cyclohexane,
[0142] More preferably, the polyol contains at least one selected from 2,5-bis(isocyanatemethyl)bicyclo-[2.2.1]-heptane, 2,6-bis(isocyanatemethyl)bicyclo-[2.2.1]-heptane, and meta-xylylene diisocyanate.
[0143] (Amine compound)
[0144] Examples of the amine compound include ethylenediamine, 1,2- or 1,3-diaminopropane, 1,2-, 1,3- or 1,4-diaminobutane, 1,5-diaminopentane, 1,6-diaminohexane, 1,7-diaminoheptane, 1,8-diaminooctane, 1,10-diaminodecane, 1,2-, 1,3- or 1,4-diaminocyclohexane, o-, m- or p-diaminobenzene, 3,4- or 4,4'-diaminobenzophenone, 3,4- or 4,4'-diaminodiphenyl ether, 4,4'-diaminodiphenylmethane, 4,4'-diamino Primary polyamine compounds such as diphenyl sulfide, 3,3'- or 4,4'-diaminodiphenyl sulfone, 2,7-diaminofluorene, 1,5-, 1,8- or 2,3-diaminonaphthalene, 2,3-, 2,6- or 3,4-diaminopyridine, 2,4- or 2,6-diaminotoluene, m- or p-phenylenediamine, isophoronediamine, diaminomethyldicycloheptane, 1,3- or 1,4-diaminomethylcyclohexane, 2- or 4-aminopiperidine, 2- or 4-aminomethylpiperidine, 2- or 4-aminoethylpiperidine, N-aminoethylmorpholine, and N-aminopropylmorpholine;
[0145] Monofunctional secondary amine compounds such as diethylamine, dipropylamine, di-n-butylamine, di-sec-butylamine, diisobutylamine, di-n-pentylamine, di-3-pentylamine, dihexylamine, dioctylamine, di(2-ethylhexyl)amine, methylhexylamine, diallylamine, N-methylallylamine, piperidine, pyrrolidine, diphenylamine, N-methylamine, N-ethylamine, dibenzylamine, N-methylbenzylamine, N-ethylbenzylamine, dicyclohexylamine, N-methylaniline, N-ethylaniline, dinaphthylamine, 1-methylpiperazine, and morpholine;
[0146] N,N'-dimethylethylenediamine, N,N'-dimethyl-1,2-diaminopropane, N,N'-dimethyl-1,3-diaminopropane, N,N'-dimethyl-1,2-diaminobutane, N,N'-dimethyl-1,3-diaminobutane, N,N'-dimethyl-1,4-diaminobutane, N,N'-dimethyl-1,5-diaminopentane, N,N'-dimethyl-1,6-diaminohexane, N,N'-dimethyl-1,7-diaminoheptane, N,N'-diethylethylenediamine, N,N'-diethyl-1,2-diaminopropane, N,N'-diethyl-1,3-diaminopropane, N,N' -diethyl-1,2-diaminobutane, N,N'-diethyl-1,3-diaminobutane, N,N'-diethyl-1,4-diaminobutane, N,N'-diethyl-1,5-diaminopentane, N,N'-diethyl-1,6-diaminohexane, N,N'-diethyl-1,7-diaminoheptane, piperazine, 2-methylpiperazine, 2,5-dimethylpiperazine, 2,6-dimethylpiperazine, homopiperazine, 1,1-di(4-piperidinyl)methane, 1,2-di(4-piperidinyl)ethane, 1,3-di(4-piperidinyl)propane, 1,4-di(4-piperidinyl)butane, tetramethylguanidine and other secondary polyamine compounds; etc.
[0147] <Polymerization Catalyst>
[0148] The polymerizable composition for an optical material according to the first embodiment contains at least one polymerization catalyst.
[0149] The polymerization catalyst is not particularly limited, and for example, a basic catalyst, an organic metal catalyst, zinc carbamate, an ammonium salt, a sulfonic acid, etc. can be used.
[0150] The above-mentioned polymerization catalysts may be used alone or in combination of two or more thereof.
[0151] (Basic Catalyst)
[0152] Examples of the basic catalyst include amine catalysts (including imidazole catalysts) and the like.
[0153] Specifically, tertiary amine catalysts such as triethylenediamine, N,N-dimethylcyclohexylamine, N,N-dicyclohexylmethylamine, N,N-dimethylethanolamine, triethylamine, and N-ethylmorpholine; 2-methylpyrazine, pyridine, α-methylpyridine, β-methylpyridine, γ-methylpyridine, 2,6-lutidine, 3,5-lutidine, 2,4,6-trimethylpyridine, 3-chloropyridine, N,N-diethylaniline, N,N-dimethylaniline, hexamethylenetetramine, quinoline, isoquinoline, N,N-dimethyl-p-toluidine, N,N-dimethylpiperazine, quinaldine, 4-methylmorpholine, triallylamine, trioctylamine, 1,2-dimethylimidazole, and 1-benzyl-2-methylimidazole.
[0154] Among the above, as the basic catalyst, an amine catalyst is preferable.
[0155] Examples of the amine catalyst include tertiary amine catalysts such as 3,5-lutidine, 2,4,6-collidine, N,N-dimethylcyclohexylamine, N,N-dicyclohexylmethylamine, triethylenediamine, N,N-dimethylethanolamine, triethylamine, and N-ethylmorpholine.
[0156] Among the above, as the basic catalyst, N,N-dimethylcyclohexylamine and N,N-dicyclohexylmethylamine are preferred.
[0157] The basic catalyst also preferably contains a compound represented by the following general formula (2) and / or a compound represented by the following general formula (3).
[0158] [Chemical formula 1]
[0159]
[0160] In the general formula (2), R1 represents a linear alkyl group having 1 to 20 carbon atoms, a branched alkyl group having 3 to 20 carbon atoms, a cycloalkyl group having 3 to 20 carbon atoms, or a halogen atom, and a plurality of R1s may be the same or different. Q represents a carbon atom or a nitrogen atom. m represents an integer of 0 to 5.
[0161] [Chemical formula 2]
[0162]
[0163] In the general formula (3), R2, R3 and R4 each independently represent a linear alkyl group having 1 to 20 carbon atoms, a branched alkyl group having 3 to 20 carbon atoms, a cycloalkyl group having 3 to 20 carbon atoms, an allyl group, or a hydrocarbon group containing a hydroxyl group.
[0164] The pKa value of the basic catalyst is preferably 5 or more, more preferably 7 or more, and even more preferably 9 or more.
[0165] The pKa value of the basic catalyst is preferably 12 or less, more preferably 11 or less.
[0166] The pKa value (acid dissociation index) can be measured, for example, by (a) the method described in The Journal of Physical Chemistry vol. 68, number 6, page 1560 (1964), (b) a method using a potentiometric automatic titrator (AT-610 (trade name) etc. manufactured by Kyoto Electronics Co., Ltd.), or by (c) the acid dissociation index described in the Chemical Handbook compiled by the Chemical Society of Japan (revised 3rd edition, June 25, 1974, published by Maruzen Co., Ltd.).
[0167] (Organometallic Catalyst)
[0168] Examples of organic metal catalysts include organic tin catalysts; organic acid salts of iron, nickel, zinc, etc.; acetylacetone complexes; catalyst compositions formed from carboxylic acid metal compounds and quaternary ammonium salt compounds; catalyst compositions formed from dicyclic tertiary amine compounds; metal catalysts in which alkoxy groups, carboxyl groups, etc. are coordinated to titanium or aluminum; and the like.
[0169] As the organometallic catalyst, among the above, an organotin catalyst is preferred.
[0170] Examples of the organotin catalyst include dibutyltin dichloride (DBC), dimethyltin dichloride (DMC), dibutyltin dilaurate (DBTDL), and dibutyltin diacetate.
[0171] The organotin catalyst preferably includes at least one selected from the group consisting of dibutyltin dichloride, dimethyltin dichloride, dibutyltin dilaurate, and dibutyltin diacetate.
[0172] The polymerization catalyst preferably contains at least one selected from the group consisting of a basic catalyst having a pKa value of 5 to 12 and an organic metal catalyst.
[0173] The polymerization catalyst also preferably contains at least one selected from the group consisting of amine-based catalysts and organotin-based catalysts.
[0174] The polymerization catalyst preferably contains at least one selected from the group consisting of N,N-dimethylcyclohexylamine, N,N-dicyclohexylmethylamine, 3,5-lutidine, 2,4,6-trimethylpyridine, triethylenediamine, N,N-dimethylethanolamine, N-ethylmorpholine, dibutyltin dichloride, dimethyltin dichloride, dibutyltin dilaurate and dibutyltin diacetate.
[0175] Among the above, it is preferred that the polymerization catalyst contains at least one selected from the group consisting of N,N-dimethylcyclohexylamine and N,N-dicyclohexylmethylamine.
[0176] In the polymerizable composition for an optical material according to the first embodiment, the content of the polymerization catalyst is 0.1150 to 0.2000 parts by mass based on the total amount of the monomers for an optical material.
[0177] Compared with the conventional method for producing an optical material, the content of the polymerization catalyst in the first embodiment is larger.
[0178] Thus, in the curing step, when the optical material monomer in the polymerizable composition for optical material is polymerized, the reaction heat of the polymerizable composition for optical material (i.e., heat generated by self-heating) can be generated in a short time. Therefore, the polymerization reaction can be well promoted, and as described later, the viscosity of the polymerizable composition can be increased, and the heat convection that is presumed to be the cause of striae can be suppressed, and a high-quality optical material can be obtained in a shorter time than before.
[0179] By making the content of the polymerization catalyst relative to the total amount of the optical material monomer be more than 0.1150 mass parts, the polymerization reaction can be promoted well, therefore, high-quality optical materials can be obtained in a short time. In addition, by promoting the polymerization reaction well, the demoulding property when the cured product is taken out from the mold can be improved.
[0180] From the above viewpoints, the content of the polymerization catalyst relative to the total amount of the monomers for an optical material is preferably 0.1175 parts by mass or more, and more preferably 0.1250 parts by mass or more.
[0181] When the content of the polymerization catalyst is 0.2000 parts by mass or less based on the total amount of the monomers for an optical material, for example, the workability when the polymerizable composition for an optical material is injected into a mold can be improved.
[0182] From the above viewpoints, the content of the polymerization catalyst relative to the total amount of the monomers for an optical material is preferably 0.1800 parts by mass or less, and more preferably 0.1500 parts by mass or less.
[0183] The content of the polymerization catalyst can be appropriately set depending on the type of the polymerization catalyst, the type and amount of monomers used (episulfide compound, other components, etc.), and the shape of the desired molded article.
[0184] The above-mentioned range of the content of the polymerization catalyst can be appropriately changed according to the types of the monomer for optical material and the polymerization catalyst.
[0185] The polymerization catalyst preferably satisfies the following condition 1.
[0186] [Condition 1]
[0187] -Ea / R is above -7100 and below -1500.
[0188] (Ea is the activation energy calculated from the reaction rate constants of two or more different monomers for optical materials at two or more different temperatures using an Arrhenius plot, and R is the gas constant (8.314 J / mol / K).)
[0189] When the polymerization catalyst satisfies condition 1, the variation in polymerization rate can be suppressed during the polymerization and curing of the polymerizable composition, and as a result, the occurrence of optical strain and striae can be suppressed, thereby obtaining an optical material having excellent appearance.
[0190] The value of Ea is calculated by the following method.
[0191] The value of Ea is calculated by performing the following steps:
[0192] A physical property acquisition step of heating a composition 1 comprising a polymerizable compound and a predetermined amount of a polymerization catalyst, and acquiring physical property values 1a derived from functional groups of the polymerizable compound before heating and physical property values 1b derived from residual functional groups after heating for a predetermined time when the composition is kept at various temperatures;
[0193] The residual functional group rate calculation step calculates the residual functional group rate 1 at the above-mentioned various temperatures from the physical property value 1a and the physical property value 1b;
[0194] a reaction rate constant calculation step of calculating the reaction rate constant 1 at the plurality of temperatures from the residual functional group ratio 1 based on a reaction rate formula; and
[0195] In the fitting step, activation energy Ea1 and frequency factor A1 are calculated from the reaction rate constant 1 at various temperatures through the Arrhenius curve.
[0196] Using the calculated Ea, it is determined whether the polymerization catalyst satisfies condition 1.
[0197] The specific aspects of the method for calculating the value of Ea and the method for determining whether the polymerization catalyst satisfies Condition 1 are the same as those described in International Publication No. 2020 / 256057.
[0198] (Other additives)
[0199] The polymerizable composition for an optical material according to the first embodiment may contain optional additives.
[0200] As optional additives, there can be mentioned photochromic compounds, internal mold release agents, bluing agents, ultraviolet absorbers, and the like.
[0201] (Photochromic Compounds)
[0202] A photochromic compound is a compound whose molecular structure changes reversibly when irradiated with light of a specific wavelength, and whose light absorption characteristics (absorption spectrum) change accordingly.
[0203] Examples of the photochromic compound used in the first embodiment include compounds whose light absorption characteristics (absorption spectrum) change with respect to light of a specific wavelength.
[0204] In the first embodiment, the photochromic compound is not particularly limited, and any compound can be appropriately selected from the known compounds that can be used for photochromic lenses. For example, one or more of spiropyran compounds, spirooxazine compounds, fulgide compounds, naphthopyran compounds, bisimidazole compounds, etc. can be used according to the desired coloring.
[0205] (Internal release agent)
[0206] Examples of the internal mold release agent include acidic phosphate esters. Examples of the acidic phosphate ester include phosphoric acid monoesters and phosphoric acid diesters, and these may be used alone or in combination of two or more.
[0207] (Bluing agent)
[0208] Examples of the bluing agent include substances that have an absorption band in the orange to yellow wavelength region in the visible light region and have a function of adjusting the hue of an optical material formed of a resin. More specifically, the bluing agent includes substances that exhibit blue to purple.
[0209] (Ultraviolet light absorber)
[0210] Examples of the ultraviolet absorber that can be used include benzophenone ultraviolet absorbers such as 2,2′-dihydroxy-4-methoxybenzophenone, triazine ultraviolet absorbers such as 2-[4-[(2-hydroxy-3-dodecyloxypropyl)oxy]-2-hydroxyphenyl]4,6-bis(2,4-dimethylphenyl)-1,3,5-triazine, and benzotriazole ultraviolet absorbers such as 2-(2H-benzotriazol-2-yl)-4-methylphenol, 2-(2H-benzotriazol-2-yl)-4-tert-octylphenol, and 2-(5-tert-butyl-2-hydroxyphenyl)benzotriazole. Preferred examples include benzotriazole ultraviolet absorbers such as 2-(5-chloro-2H-benzotriazol-2-yl)-4-methyl-6-tert-butylphenol and 2-(5-tert-butyl-2-hydroxyphenyl)benzotriazole. These ultraviolet absorbers may be used alone or in combination of two or more.
[0211] (Viscosity)
[0212] For the polymerizable composition for optical materials of the first embodiment, from the viewpoint of suppressing wave lines, the viscosity measured by a B-type viscometer under the conditions of 20°C and 60 rpm is 10 mPa·s or more, preferably 20 mPa·s or more, more preferably 40 mPa·s or more, further preferably 80 mPa·s or more, particularly preferably 100 mPa·s or more, and further preferably 120 mPa·s or more.
[0213] For the polymerizable composition for optical materials of the first embodiment, from the viewpoint of maintaining good operability when molding the optical material into a desired shape, the viscosity measured by a B-type viscometer at 20° C. and 60 rpm is 1000 mPa·s or less, preferably 700 mPa·s or less, and more preferably 400 mPa·s or less.
[0214] The viscosity of the polymerizable composition for an optical material according to the first embodiment can be adjusted according to the intended use of the obtained cured product.
[0215] For example, when a cured product is obtained using a mold for a convex lens, the end face (i.e., the injection port) is narrow (e.g., 1 mm to 3 mm). Therefore, for the polymerizable composition for optical material of the first embodiment, from the perspective of suppressing ribs, the above-mentioned viscosity is preferably 10 mPa·s to 100 mPa·s.
[0216] On the other hand, when a cured product is obtained using a mold for a conventional lens other than a convex lens, the end face (i.e., the injection port) is wide (e.g., 5 mm to 15 mm). Therefore, for the polymerizable composition for optical material of the first embodiment, from the viewpoint of suppressing wave lines, the above-mentioned viscosity is preferably 10 mPa·s to 1000 mPa·s, and more preferably 30 mPa·s to 1000 mPa·s.
[0217] By increasing the viscosity of the polymerizable composition for an optical material, when the composition is heated from the outside, heat convection caused by the temperature difference between the inside and the outside of the composition can be suppressed, and striae caused by heat convection can be reduced.
[0218] However, when the amount of catalyst is small, the thickening rate during polymerization is insufficient, so the viscosity does not increase to a level that can suppress heat convection, and the temperature cannot be raised rapidly in a short time. In addition, the time required until the polymerization is completed also becomes longer.
[0219] On the other hand, according to the present disclosure, the amount of catalyst is increased to an optimal range in consideration of the reactivity of the episulfide compound, thereby increasing the viscosity of the entire composition more rapidly. This can suppress uneven polymerization and thermal convection caused by a rapid temperature rise, thereby enabling polymerization to proceed in a short time.
[0220] (Thixotropic ratio)
[0221] The thixotropic ratio of the polymerizable composition for an optical material according to the first embodiment is preferably 1.3 or less, more preferably 1.2 or less, and even more preferably 1.1 or less.
[0222] By setting the thixotropic ratio of the polymerizable composition for optical material of the first embodiment to be 1.3 or less, the composition can be quickly filled into a polymerization container such as a mold described later, and heat convection during polymerization can be suppressed, and the generation of striae, etc. in the monomer for optical material can be further prevented. As a result, the generation of striae, etc. can be suppressed in the obtained optical material, and the quality can be well maintained.
[0223] The thixotropic ratio of the polymerizable composition for an optical material according to the first embodiment is preferably 0.9 or more, more preferably 0.95 or more, and even more preferably 1.0 or more.
[0224] The thixotropic ratio can be calculated by dividing the viscosity η1 measured at 20° C. and a rotation speed of 6 rpm by the viscosity η2 measured at a rotation speed of 60 rpm using a B-type viscometer.
[0225] For example, the thixotropic ratio can be reduced by reducing the molecular weights of two or more monomers for optical materials, suppressing the degree of polymerization of the prepolymer to a certain value or less, or reducing the ratio of the structure providing elasticity in the monomer.
[0226] Preferably, the polymerizable composition for an optical material of the first embodiment comprises two or more different monomers for an optical material, a polymerization catalyst, and a prepolymer having a polymerizable functional group, wherein the prepolymer having a polymerizable functional group is a polymer of the two or more different monomers for an optical material, and at least one of the two or more different monomers for an optical material is an episulfide compound.
[0227] The prepolymer is a polymer of two or more different monomers for optical materials, and is a polymer having a polymerizable functional group.
[0228] A cured product obtained by polymerizing a prepolymer with two or more different monomers for an optical material can be used as an optical material.
[0229] Examples of the prepolymer include a polymer obtained by polymerizing two optical material monomers without polymerizing polymerizable functional groups at an equivalent ratio of 1:1; and a polymer obtained by polymerizing two optical material monomers at an unbalanced equivalent ratio.
[0230] 《Polymerizable prepolymer composition for optical materials》
[0231] The polymerizable prepolymer composition for optical material of the first embodiment is a composition comprising a prepolymer having a polymerizable functional group and a polymerization catalyst, wherein the prepolymer having a polymerizable functional group is a polymer of two or more different monomers for optical material, at least one of the two or more different monomers for optical material is an episulfide compound, and the viscosity of the polymerizable prepolymer composition for optical material measured by a B-type viscometer at 20° C. and 60 rpm is 10 mPa·s to 1000 mPa·s.
[0232] It should be noted that it is preferred that the viscosity of the prepolymer composition does not easily change over time (that is, is stable).
[0233] The fact that the viscosity of the prepolymer composition is stable means that when the prepolymer composition is stored at 20° C. for 24 hours, the change in viscosity before and after the storage is 10% or less.
[0234] Specific examples, preferred specific examples, preferred aspects, etc. of the monomer for optical material and the polymerization catalyst of the polymerizable prepolymer composition for optical material are the same as the specific examples, preferred specific examples, preferred aspects, etc. of the monomer for optical material and the polymerization catalyst described in the section of the polymerizable composition for optical material.
[0235] The definition of the prepolymer in the polymerizable prepolymer composition for an optical material is the same as the definition of the prepolymer described in the section of the polymerizable composition for an optical material.
[0236] In the polymerizable prepolymer composition for an optical material according to the first embodiment, the content of the polymerization catalyst is preferably 0.01 to 0.2 parts by mass based on 100 parts by mass of the total prepolymer.
[0237] By making the content of the aforementioned polymerization catalyst relative to a total of 100 parts by mass of the aforementioned prepolymer to be more than 0.01 parts by mass, the polymerization reaction can be promoted well, and therefore, a high-quality optical material can be obtained in a short time. In addition, by promoting the polymerization reaction well, the demoulding property when the cured product is taken out from the mold can be improved.
[0238] From the above viewpoints, the content of the polymerization catalyst relative to 100 parts by mass of the total of the prepolymer is preferably 0.02 parts by mass or more, and more preferably 0.03 parts by mass or more.
[0239] When the content of the polymerization catalyst is 0.2 parts by mass or less based on 100 parts by mass of the total prepolymer, for example, workability when the polymerizable composition for an optical material is injected into a mold can be improved.
[0240] From the above viewpoints, the content of the polymerization catalyst relative to 100 parts by mass of the total prepolymer is preferably 0.18 parts by mass or less, more preferably 0.16 parts by mass or less, and even more preferably 0.14 parts by mass or less.
[0241] (Thixotropic ratio)
[0242] The thixotropic ratio of the polymerizable prepolymer composition for an optical material according to the first embodiment is preferably 1.3 or less, more preferably 1.2 or less, and even more preferably 1.1 or less.
[0243] By making the thixotropic ratio of the polymerizable prepolymer composition for optical material of the first embodiment 1.3 or less, the composition can be quickly filled into a polymerization container such as a mold described later, and the heat convection during polymerization can be suppressed, and the generation of ribs, etc. in the monomer for optical material can be further prevented. As a result, the generation of ribs, etc. can be suppressed in the obtained optical material, and the quality can be well maintained.
[0244] The thixotropic ratio of the polymerizable composition for an optical material according to the first embodiment is preferably 0.9 or more, more preferably 0.95 or more, and even more preferably 1.0 or more.
[0245] The method for measuring the thixotropic ratio is as described above.
[0246] For the polymerizable prepolymer composition for optical material of the first embodiment, the value obtained by subtracting the refractive index B of the prepolymer raw material composition (which is a composition before forming a prepolymer and contains the aforementioned two or more different monomers for optical material and a polymerization catalyst) from the refractive index A of the polymerizable prepolymer composition for optical material (also referred to as "refractive index A-refractive index B") is preferably greater than 0, more preferably greater than 0.001, and further preferably greater than 0.005.
[0247] The refractive index A is the refractive index of the optical material polymerizable prepolymer composition obtained by polymerizing the optical material monomer and the polymerization catalyst to obtain the prepolymer, and the refractive index B is the refractive index of the prepolymer raw material composition before polymerizing the optical material monomer and the polymerization catalyst to obtain the prepolymer.
[0248] By making the refractive index A-refractive index B within the above range, it is easy to adjust the polymerizable composition for optical material to a predetermined viscosity. In addition, it is easy to stabilize the quality (eg, refractive index, appearance, etc.) of the cured product of the polymerizable composition for optical material.
[0249] The refractive index A-refractive index B may be 0.020 or less, or 0.010 or less.
[0250] "Solidified Object"
[0251] The cured product of the first embodiment is a cured product of the polymerizable composition for an optical material of the first embodiment or the polymerizable prepolymer composition for an optical material of the first embodiment.
[0252] For the cured product of the first embodiment, from the viewpoint of reducing striae, when an amine catalyst is used as a polymerization catalyst, the amine content is preferably 0.01 mass % or more, more preferably 0.02 mass % or more, further preferably 0.04 mass % or more, and particularly preferably 0.06 mass % or more.
[0253] In addition, in the cured product of the first embodiment, the amine content is preferably 0.20 mass % or less, more preferably 0.18 mass % or less, and even more preferably 0.15 mass % or less, from the viewpoint of improving the handleability of the polymerizable composition for an optical material.
[0254] The above-mentioned amine content is the amine content measured by gas chromatography-mass spectrometry from a methylene chloride composition obtained by dispersing the solidified material in methylene chloride and subjecting the mixture to ultrasonic extraction.
[0255] The method for measuring the amine content in the cured product is as follows.
[0256] 200 mg of the solidified material formed into powder by filing and 3 mL of dichloromethane were placed in a centrifuge tube (volume 10 mL), and ultrasonic extraction was performed at room temperature for 10 minutes using an ultrasonic washing machine (manufactured by IUCHI, US-4). Centrifugal separation was performed at 4000 rpm for 10 minutes using a centrifuge (manufactured by KUBOTA, tabletop small centrifuge 2410).
[0257] The supernatant was collected, and the residue was dispersed again in 3 mL of dichloromethane, and the above-mentioned ultrasonic extraction and centrifugal separation were performed to collect the supernatant (hereinafter also referred to as "residue extraction").
[0258] After the above-mentioned residue extraction was further performed twice, dichloromethane was added to the obtained supernatant to adjust the total amount to 10 mL.
[0259] The obtained 10 mL supernatant was filtered and analyzed by gas chromatography-mass spectrometry (also referred to as GC-MS) (GC-MS apparatus: Agilent, 6890GC / 5973N MSD, column: CP-Sil 8CB for Amine (0.25 mmID×30 m FT=0.25 μm)) to obtain the peak area value derived from amines. A calibration curve of the obtained peak area value derived from amines and the amount of amines was prepared to measure the content of amines in the cured product.
[0260] In addition, the said amine means an amine compound which can be used as a polymerization catalyst, or an amine compound derived from the said amine compound.
[0261] In particular, in optical applications requiring light transmittance, the devitrification degree of the cured product of the first embodiment is preferably less than 50, and more preferably less than 35.
[0262] The devitrification can be measured by the following method.
[0263] Light from a light source (e.g., Luminar Ace LA-150A manufactured by Hayashi-Repic Co., Ltd.) is made to pass through the cured product in a dark place. An image of the light passing through the cured product is collected in an image processing device (e.g., an image processing device manufactured by Ube Information Systems Inc.), and the collected image is subjected to shading processing. The shading degree of the processed image is numerically converted for each pixel, and the value calculated as the average value of the shading degree of each pixel is used as the devitrification value.
[0264] For the cured product of the first embodiment, preferably there are no ribs longer than 1.0 mm within a radius of 15 mm from the center of the cured product, and more preferably there are no ribs longer than 1.0 mm within and outside a radius of 15 mm from the center of the cured product.
[0265] More specifically, the cured product of the first embodiment may be a cured product of two or more different monomers for optical use, at least one of the two or more different monomers for optical materials is an episulfide compound, no ribs having a length of 1.0 mm or more are present within a radius of 15 mm from the center of the cured product, and the amine content measured by gas chromatography-mass spectrometry is 0.01% by mass or more and 0.20% by mass or less.
[0266] 《Methods for producing optical materials》
[0267] The method for producing an optical material according to the first embodiment includes the following production method A and production method B.
[0268] <Production Method A>
[0269] Preparation method A includes the following steps: a preparation step of preparing a polymerizable composition for an optical material, wherein the polymerizable composition for an optical material comprises two or more different monomers for an optical material, and a polymerization catalyst, wherein at least one of the two or more different monomers for an optical material is an episulfide compound, and the content of the polymerization catalyst relative to the total amount of the two or more different monomers for an optical material is 0.1150 to 0.2000 parts by mass; a casting step of adjusting the viscosity of the polymerizable composition for an optical material measured at 20° C. and 60 rpm using a B-type viscometer to 10 to 1000 mPa·s, and casting the composition into a mold; and a curing step of curing the polymerizable composition for an optical material by polymerizing the two or more different monomers for an optical material in the polymerizable composition for an optical material in the mold.
[0270] The production method A includes the preparation step, the casting step, and the curing step, so that the quality of the obtained optical material can be maintained and the production time of the optical material can be shortened.
[0271] The manufacturing method A may include the above-mentioned preparation step, the casting step, and the above-mentioned curing step in sequence.
[0272] The content of the polymerization catalyst in the polymerizable composition for optical material prepared in the preparation step in the preparation method A is 0.1150 to 0.2000 parts by mass relative to the total amount of the two or more different monomers for optical material. This content of the polymerization catalyst is larger than that in conventional optical material production methods.
[0273] Thus, in the curing step, when the optical material monomers in the polymerizable composition for optical material are polymerized, reaction heat of the polymerizable composition for optical material (ie, heat generated by self-heating) can be generated in a short time.
[0274] The above reaction heat can be utilized to promote the polymerization reaction of the monomers for optical materials in the polymerizable composition for optical materials, so that a high-quality optical material can be obtained in a shorter time than before.
[0275] Conventionally, when performing a polymerization reaction, the polymerizable composition for an optical material is mainly heated to allow the polymerization reaction to proceed. However, in the production method A, heating of the polymerizable composition for an optical material is not essential.
[0276] In addition, in the preparation method A, since the self-heating of the composition is also utilized, the polymerization can be carried out without excessive reliance on heat supplied from the outside. Therefore, not only the viscosity of the composition described later can be increased, but also the thermal non-uniformity and thermal convection in the polymerizable composition for optical materials can be suppressed, and the occurrence of striae can be suppressed.
[0277] It should be noted that in the present disclosure, the so-called ribs are a state where the refractive index of a specific part is different from the normal refractive index of the surrounding part. In addition, it can also be manifested as a state that is unfavorable in the intended use of the optical material. In optical materials, ribs are a defect.
[0278] <Preparation process>
[0279] Preparation method A includes: a preparation step of preparing a polymerizable composition for an optical material, wherein the polymerizable composition for an optical material comprises two or more different monomers for an optical material, and a polymerization catalyst, at least one of the two or more different monomers for an optical material is an episulfide compound, and the content of the polymerization catalyst relative to the total amount of the two or more different monomers for an optical material is 0.1150 to 0.2000 parts by mass.
[0280] The preparation step may be a step of simply preparing a previously manufactured polymerizable composition for an optical material, or may be a step of manufacturing the polymerizable composition for an optical material.
[0281] In the preparation step, the polymerizable composition for an optical material is not particularly limited as long as it contains two or more different monomers for an optical material and a polymerization catalyst.
[0282] As the polymerizable composition for optical material, a ready-made product may be used, or at least two or more different monomers for optical material and a polymerization catalyst may be mixed to prepare the same.
[0283] The mixing method is not particularly limited, and a known method can be used.
[0284] The temperature at the time of mixing the above-mentioned components is not particularly limited, but is preferably 30° C. or lower, and more preferably room temperature (25° C.) or lower.
[0285] From the viewpoint of the storage life of the prepared polymerizable composition for optical material, it is sometimes preferable to set the temperature lower than 25° C. However, when additives such as internal mold release agents have poor solubility in the above components, the above components may be heated in advance to dissolve the additives in the above components.
[0286] When mixing the above-mentioned components, it is preferably carried out under a dry inert gas in order to prevent water from being mixed into the polymerizable composition for an optical material.
[0287] The preparation step is preferably a step of preparing the polymerizable composition for an optical material by mixing the two or more different monomers for an optical material in advance and then mixing the polymerization catalyst.
[0288] Thus, before the above-mentioned mixture of two or more different monomers for optical material is mixed with the above-mentioned polymerization catalyst, the polymerization of the above-mentioned two or more different monomers for optical material can be prevented from proceeding.
[0289] Therefore, by performing the preparation steps in the above order, the polymerization start timing can be adjusted. Therefore, for example, the workability when the polymerizable composition for an optical material is injected into a mold can be improved.
[0290] As a specific aspect of the preparation step, for example, the following aspects can be mentioned.
[0291] First, monomers for optical materials and additives (such as internal mold release agents) are charged to prepare a mixed solution, and the mixed solution is stirred at 25° C. for 1 hour to completely dissolve the components, thereby obtaining a mixed solution.
[0292] Then, a polymerization catalyst is added to the mixed solution, and the mixture is stirred to completely dissolve the mixture, thereby obtaining a polymerizable composition for an optical material as a uniform solution.
[0293] <Casting process>
[0294] The preparation method A includes a casting step of adjusting the viscosity of the polymerizable composition for an optical material to 10 to 1000 mPa·s as measured by a Brookfield viscometer at 20° C. and 60 rpm, and casting the composition into a mold.
[0295] By adjusting the viscosity of the polymerizable composition for optical material to within the above range and performing casting, the viscosity of the polymerizable composition for optical material produced in the process of producing the polymerizable composition for optical material can be within an appropriate range from the viewpoint of suppressing striae in the obtained optical material.
[0296] From the above viewpoints, the viscosity of the polymerizable composition for optical material is 10 mPa·s or more, preferably 20 mPa·s or more, more preferably 40 mPa·s or more, further preferably 80 mPa·s or more, particularly preferably 100 mPa·s or more, and further preferably 120 mPa·s or more.
[0297] From the viewpoint of maintaining good workability when molding an optical material into a desired shape, the viscosity of the polymerizable composition for an optical material is 1000 mPa·s or less, preferably 700 mPa·s or less, and more preferably 400 mPa·s or less.
[0298] There is no particular limitation on the method for adjusting the viscosity of the polymerizable composition for an optical material.
[0299] For example, the viscosity of the polymerizable composition for an optical material can be adjusted by adding a high-viscosity compound, heating, stirring, or the like.
[0300] <Curing process>
[0301] The manufacturing method A includes a curing step of curing the polymerizable composition for optical material by polymerizing the two or more different monomers for optical material in the polymerizable composition for optical material in the mold.
[0302] The production method A includes a curing step, whereby the polymerizable composition for an optical material can be polymerized to produce an optical material.
[0303] Conventionally, when a polymerization reaction is carried out, the polymerizable composition for optical material is heated to cause the polymerization reaction to occur. However, for the polymerizable composition for optical material in Preparation Method A, the polymerization reaction of the optical material monomer in the polymerizable composition for optical material can be promoted by generating reaction heat accompanying the polymerization reaction (i.e., heat generated due to self-heating) in a short period of time.
[0304] Therefore, in the preparation method A, heating of the polymerizable composition for an optical material is not essential, but heating may be performed.
[0305] That is, in the curing step of the production method A, the polymerizable composition for an optical material can be cured by polymerization by leaving the polymerizable composition for an optical material to stand.
[0306] The environment in which the curing process is carried out is not particularly limited. Although the mold can also be heated from the outside to perform curing, from the perspective of improving the optical quality of the ribs and the like while performing polymerization in a short time, the following process is preferred: the aforementioned polymerizable composition for optical material is cured by allowing the aforementioned polymerizable composition for optical material to stand in a closed space.
[0307] By leaving the polymerizable composition for optical material at rest in a closed space, it is possible to prevent the heat generated by the self-heating of the polymerizable composition for optical material from being released to the outside. Thus, the heat generated by the self-heating can be kept in the closed space, so that the polymerization reaction can be promoted more efficiently, and the optical material can be manufactured in a shorter time.
[0308] An example of a closed space is a heat-insulating environment.
[0309] The so-called heat-insulating environment refers to an environment that keeps heat inside and suppresses heat conduction between the inside and the outside. The so-called environment that suppresses heat conduction between the inside and the outside refers to an environment in which, when the polymerizable composition for optical material is left to stand in a closed space, the heat conductivity between the inside and the outside of the closed space is such that the polymerizable composition for optical material can be cured.
[0310] The heat-insulating environment may be formed using, for example, a heat-insulating material.
[0311] That is, by allowing the polymerizable composition for an optical material to stand in a heat-insulating container formed of a heat-insulating material, heat can be retained inside the heat-insulating container, and heat conduction between the inside and the outside can be suppressed.
[0312] The thermal conductivity of the heat insulating material is preferably 0.50 W / mK or less, more preferably 0.10 W / mK or less, and further preferably 0.05 W / mK or less.
[0313] The density of the insulation material is preferably 10 kg / m 3 More preferably 15kg / m 3 More preferably, 20 kg / m 3 above.
[0314] In the "insulation" or "insulation environment" in Preparation A, it is preferred to heat the insulation reaction tank to a constant temperature state (constant temperature reaction tank) within a range that does not hinder the polymerization reaction based on the reaction heat of the polymerizable composition for optical materials or excessively promote the polymerization reaction of the polymerizable composition for optical materials due to external heating.
[0315] Thus, the ambient temperature in the reaction vessel (constant temperature reaction vessel) where the mold is placed can be kept warm or kept constant by the temperature rise due to the self-heating of the monomer for optical material, thereby promoting the polymerization reaction more effectively.
[0316] As the heat-insulating environment, for example, the above-mentioned heat-insulating reaction tank or constant-temperature reaction tank can be used.
[0317] For example, when the mold injected with the monomer is left to stand in a vacuum container as an insulating reaction tank, adiabatic polymerization can be performed in the following procedure in an insulating environment using the insulating reaction tank (constant temperature reaction tank).
[0318] The inner side of the vacuum container is covered with a member having heat insulation and heat preservation properties such as polyurethane foam and cork, and the mold injected with the monomer is wrapped with a member such as cloth as needed. Then, the mold injected with the monomer is left to stand in the vacuum container.
[0319] The curing step may be a step of curing the polymerizable composition for an optical material by leaving the polymerizable composition for an optical material to stand without external heating.
[0320] As described above, in the preparation method A, heating of the polymerizable composition for an optical material is not essential.
[0321] In order to heat from the outside, a device may be used, and the economic burden may increase. According to the production method A, the optical material can be produced by a simple method, so the economic burden can be reduced.
[0322] The curing step is preferably a step of curing the polymerizable composition for an optical material by leaving the polymerizable composition for an optical material to stand for 6 to 20 hours.
[0323] According to the conventional method, the polymerization reaction is generally carried out over several hours to several tens of hours (for example, about 20 hours to 48 hours) while gradually raising the temperature by heating.
[0324] When the polymerization reaction is performed for a short time, the polymerizable composition for an optical material is not completely cured, and therefore, an optical material cannot be obtained, or the quality of the optical material is deteriorated.
[0325] However, the optical material can be produced in a short time while maintaining the quality of the obtained optical material according to Production Method A. Specifically, the optical material can be produced by allowing the polymerizable composition for an optical material to stand for 20 hours or less.
[0326] From the above viewpoints, in the curing step, it is more preferred that the polymerizable composition for an optical material be left to stand for 16 hours or less.
[0327] From the viewpoint of allowing the polymerization reaction to proceed and obtaining a well-cured optical material, the polymerizable composition for an optical material is preferably left to stand for 7 hours or more, more preferably for 9 hours or more.
[0328] In the curing step, a microwave irradiation step of irradiating the polymerizable composition for an optical material with microwaves for a predetermined time may be provided as necessary.
[0329] As one aspect of the curing step, there is mentioned an aspect including the following steps a and b.
[0330] Step a: Injecting (casting) the polymerizable composition for an optical material into a mold (inside the cavity of a mold).
[0331] Step b: The mold into which the polymerizable composition for an optical material is injected is left to stand in a closed space for a predetermined period of time to perform heat-insulating polymerization.
[0332] (Process a)
[0333] First, the polymerizable composition is injected into a molding die (casting mold) held by a gasket or tape, etc. At this time, degassing treatment under reduced pressure, filtration treatment under pressure or reduced pressure, etc. are preferably performed as needed, depending on the physical properties required for the obtained optical material.
[0334] (Process b)
[0335] The polymerization conditions are not limited, but are preferably appropriately adjusted according to the composition of the polymerizable composition for an optical material, the type and amount of the catalyst used, the shape of the mold, and the like.
[0336] The mold into which the polymerizable composition for optical material is injected may be left to stand for 6 to 20 hours in a heat-insulating environment, thereby polymerizing the optical material monomer in the polymerizable composition for optical material.
[0337] In step b, if necessary, a heating step may be added after the heat insulation polymerization process in which the mold into which the polymerizable composition for an optical material is injected is left to stand for a certain period of time in a heat insulation environment.
[0338] In step b, if necessary, in parallel with the step of leaving the mold injected with the polymerizable composition for optical material to stand in a heat-insulating environment (thermal insulation polymerization), the mold injected with the polymerizable composition for optical material can be heated continuously or intermittently at a temperature not higher than the self-heating generated by the polymerizable composition for optical material in the thermal insulation polymerization process, or the inside of the thermal insulation reaction tank can be heated to keep the ambient temperature in the thermal insulation reaction tank warm.
[0339] <Annealing process>
[0340] If necessary, the method A may include an annealing step of annealing the cured polymerizable composition for an optical material.
[0341] The annealing treatment is usually performed at a temperature of 50 to 150°C, preferably 90 to 140°C, and more preferably 100 to 130°C.
[0342] <Other Process>
[0343] For the production method A, other steps may be provided as required.
[0344] As another step, when an optical material is produced using a mold, for example, there may be mentioned an injection step of injecting the polymerizable composition for an optical material into the mold.
[0345] <Applications of optical materials>
[0346] The optical material in the preparation method A can be used for plastic lenses, prisms, optical fibers, information recording substrates, optical filters, light-emitting diodes, and the like.
[0347] Among the above, the optical material in the first embodiment can be suitably used for a plastic lens, and can be more suitably used for a plastic lens for spectacles.
[0348] <Method B>
[0349] Preparation method B includes the following steps: a preparation step of preparing two or more different monomers for optical materials and a polymerization catalyst in an amount of 0.1150 to 0.2000 parts by mass based on the total amount of the two or more different monomers for optical materials; and a prepolymerization step of mixing at least a part of the two or more different monomers for optical materials and at least a part of the polymerization catalyst, polymerizing at least a part of the two or more different monomers for optical materials to obtain a prepolymer, thereby obtaining a mixture containing the prepolymer, wherein at least one of the two or more different monomers for optical materials is an episulfide compound.
[0350] The production method B includes a preparation step and a prepolymerization step, so that striae in the obtained optical material can be suppressed and the production time of the optical material can be shortened.
[0351] The preparation method B preferably includes the following steps in addition to the above-mentioned preparation step and prepolymerization step: a step of producing a polymerizable composition for an optical material, wherein the remaining portion of the polymerization catalyst or a mixture of the remaining portion of the two or more different monomers for an optical material and the remaining portion of the polymerization catalyst is added to the mixture containing the above-mentioned prepolymer, thereby obtaining a polymerizable composition for an optical material containing the above-mentioned two or more different monomers for an optical material, the above-mentioned prepolymer, and the above-mentioned polymerization catalyst; and
[0352] The curing step is to obtain an optical material which is a cured product of the polymerizable composition for optical material by curing the two or more different monomers for optical material in the polymerizable composition for optical material.
[0353] The production method B includes a step of producing a polymerizable composition for an optical material and a step of curing in addition to the preparation step and the prepolymerization step, so that striae in the obtained optical material can be more effectively suppressed and the production time of the optical material can be more effectively shortened.
[0354] The content of the polymerizable composition for optical material prepared in the preparation step in the preparation method B is 0.1150 to 0.2000 parts by mass relative to the total amount of the two or more different monomers for optical material. As in the case of the preparation method A, the content of the polymerization catalyst is larger than that of the conventional optical material production method.
[0355] Therefore, similarly to the case of the manufacturing method A, a high-quality optical material with suppressed striae can be obtained in a shorter time than before.
[0356] As in the case of the production method A, in the production method B, heating of the polymerizable composition for an optical material is not essential.
[0357] In addition, the method B includes a preparation step, a prepolymerization step, a step of producing a polymerizable composition for an optical material, and a curing step, thereby being able to suppress convection in a mold where a polymerization reaction is performed, and suppressing the generation of striae in the obtained cured product.
[0358] Furthermore, since the production method B includes the prepolymerization step, the storage stability of the mixture containing the prepolymer (for example, the polymerizable composition for an optical material) can be maintained more satisfactorily than when the prepolymerization is not performed.
[0359] For example, when a mixture containing a prepolymer is stored for a certain period of time, the polymerization reaction in the mixture can be suppressed. That is, a longer storage period can be ensured.
[0360] <Preparation process>
[0361] The preparation method B includes a preparation step of preparing two or more different monomers for optical materials and a polymerization catalyst in an amount of 0.1150 to 0.2000 parts by mass based on the total amount of the two or more different monomers for optical materials.
[0362] In the preparation step, two or more different monomers for an optical material and a polymerization catalyst in an amount of 0.1150 to 0.2000 parts by mass based on the total amount of the two or more different monomers for an optical material are prepared.
[0363] That is, the preparation method B uses two or more different monomers for optical materials and a polymerization catalyst in an amount of 0.1150 to 0.2000 parts by mass based on the total amount of the two or more different monomers for optical materials.
[0364] By using a polymerization catalyst having a content of 0.1150 parts by mass or more relative to the total amount of two or more different monomers for optical materials, the polymerization reaction can be well promoted, and thus, a high-quality optical material with suppressed ribs can be obtained in a short time. In addition, by well promoting the polymerization reaction, the demoulding property of the cured product when it is taken out of the mold can be improved.
[0365] From the above viewpoints, the polymerization catalyst is preferably used in an amount of 0.1175 parts by mass or more, more preferably 0.125 parts by mass or more, based on the total amount of the two or more different monomers for an optical material.
[0366] By using a polymerization catalyst in an amount of 0.2000 parts by mass or less based on the total amount of two or more different monomers for an optical material, for example, workability when injecting the polymerizable composition for an optical material into a mold can be improved.
[0367] From the above viewpoints, the polymerization catalyst is preferably used in an amount of 0.1800 parts by mass or less, and more preferably 0.1500 parts by mass or less, based on the total amount of two or more different monomers for an optical material.
[0368] The amount of the polymerization catalyst can be appropriately set depending on the type of the polymerization catalyst, the type and amount of monomers used (episulfide compound, other components, etc.), and the shape of the desired molded article.
[0369] <Prepolymerization process>
[0370] Preparation method B includes: a prepolymerization step of mixing at least a portion of two or more different monomers for optical materials and at least a portion of a polymerization catalyst, polymerizing at least a portion of the two or more different monomers for optical materials to obtain a prepolymer, thereby obtaining a mixture containing the prepolymer.
[0371] The inventors of the present application believe that convection occurs due to uneven temperature distribution in a mold where a polymerization reaction is performed, which is one of the causes of striae in the obtained cured product.
[0372] Therefore, the inventors of the present application focused on preparing a prepolymer by polymerizing a part of the monomers for optical materials in advance and including the prepolymer in the polymerizable composition for optical materials, thereby increasing the viscosity of the polymerizable composition for optical materials. This can suppress convection in the mold.
[0373] In the manufacturing method B, since the self-heat is not dissipated to the outside, the temperature difference between the inside and the periphery of the mold can be less likely to occur.
[0374] Based on the above viewpoints, it can be inferred that Preparation Method B can suppress striae in the obtained cured product.
[0375] Preparation method B can obtain a prepolymer with excellent shelf life by including all of one optical material monomer among two or more different optical material monomers, all or part of other optical material monomers other than the one optical material monomer, and all or part of the polymerization catalyst in the prepolymerization step.
[0376] The aspect of "a part of two or more different monomers for optical materials" is not particularly limited.
[0377] For example, “a part of two or more different monomers for an optical material” may be the amount of a part of each of two or more different monomers for an optical material.
[0378] Furthermore, “a part of two or more different monomers for an optical material” may be all of one or more of the two or more different monomers for an optical material.
[0379] In the prepolymerization step, a part or all of the polymerization catalyst may be used.
[0380] When a part of the monomers is used as a polymerization catalyst, similarly to the “part of the two or more different monomers for optical material”, the form of “a part of the polymerization catalyst” is not particularly limited.
[0381] For example, "a portion of a polymerization catalyst" may be an amount of a portion of a polymerization catalyst.
[0382] When a part of the polymerization catalyst is used, from the viewpoint of ensuring a long-term storage period, the part of the polymerization catalyst is preferably 5 to 80 parts by mass, more preferably 10 to 60 parts by mass, and further preferably 15 to 50 parts by mass in 100 parts by mass of the polymerization catalyst.
[0383] From the viewpoint of ensuring a long storage period, a portion of the two or more different monomers for optical materials is preferably 5 to 95 parts by mass, more preferably 10 to 80 parts by mass, and further preferably 20 to 70 parts by mass, out of 100 parts by mass of the two or more different monomers for optical materials.
[0384] The preparation method B preferably includes a prepolymerization step of mixing all of two or more different monomers for optical materials and a part of a polymerization catalyst, polymerizing at least a part of the two or more different monomers for optical materials to obtain a prepolymer, thereby obtaining a mixture containing the prepolymer.
[0385] Although specific examples of the prepolymerization step are shown below, the prepolymerization step in the production method B is not limited to the following aspects.
[0386] (Method a)
[0387] The prepolymerization step of embodiment a is a step of mixing a part of two or more different monomers for optical materials and all of a polymerization catalyst, polymerizing at least a part of the two or more different monomers for optical materials to obtain a prepolymer, thereby obtaining a mixture containing the prepolymer.
[0388] In aspect a, part of the two or more different monomers for an optical material is preferably formed from the whole of one of the two or more different monomers for an optical material and part of other monomers for an optical material other than the one monomer for an optical material.
[0389] (Method b)
[0390] The prepolymerization step of embodiment b is a step of mixing a part of two or more different monomers for optical materials and a part of a polymerization catalyst, polymerizing at least a part of the two or more different monomers for optical materials to obtain a prepolymer, thereby obtaining a mixture containing the prepolymer.
[0391] When the preparation method B includes the prepolymerization step of method b, the optical material polymerizable composition preparation step described later is the following step: adding at least the remaining part of two or more different optical material monomers and the remaining part of the polymerization catalyst to the mixture containing the prepolymer, thereby obtaining a polymerizable composition for optical materials containing two or more different optical material monomers, a prepolymer, and a polymerization catalyst.
[0392] <Viscosity adjustment process>
[0393] The production method B preferably includes a viscosity adjustment step of adjusting the viscosity of the mixture containing the prepolymer to 10 mPa·s to 1000 mPa·s after the prepolymerization step and before the step of producing the polymerizable composition for an optical material.
[0394] By setting the viscosity of the mixture containing the prepolymer within the above range, the viscosity of the polymerizable composition for optical material produced in the step of producing the polymerizable composition for optical material can be set within an appropriate range from the viewpoint of suppressing striae in the obtained optical material. As a result, striae in the obtained optical material can be suppressed.
[0395] From the above viewpoints, the viscosity of the mixture containing the prepolymer is preferably 40 mPa·s to 1000 mPa·s, and more preferably 50 mPa·s to 800 mPa·s.
[0396] The viscosity was measured using a B-type viscometer at 20° C. and 60 rpm (revolutions per minute).
[0397] There is no particular limitation on the method for adjusting the viscosity of the mixture containing the prepolymer.
[0398] For example, the viscosity of the mixture containing the prepolymer can be adjusted by adding a high-viscosity compound, heating, stirring, or the like.
[0399] The temperature for preparing the mixture containing the prepolymer is not particularly limited as long as it is a temperature at which the prepolymer can be obtained by the polymerization reaction, and may be, for example, 20°C to 50°C, or 25°C to 45°C.
[0400] The stirring time for preparing the mixture containing the prepolymer is not particularly limited as long as it is a stirring time that can obtain the prepolymer by the polymerization reaction, and may be, for example, 30 minutes to 10 hours, or 1 hour to 10 hours.
[0401] Specifically, the method for preparing a mixture containing a prepolymer may be a method of preparing a mixture containing a prepolymer while adjusting the viscosity by stirring the mixture at 20° C. for 6 hours.
[0402] <Process for producing polymerizable composition for optical material>
[0403] Preparation method B includes: a step of preparing a polymerizable composition for an optical material, wherein the remaining portion of the aforementioned polymerization catalyst, or a mixed solution of the remaining portion of the aforementioned two or more different monomers for an optical material and the remaining portion of the aforementioned polymerization catalyst (also referred to as the remaining portion of the polymerization catalyst, etc. in this disclosure) is added to a mixture containing a prepolymer, thereby obtaining a polymerizable composition for an optical material containing two or more different monomers for an optical material, a prepolymer, and a polymerization catalyst.
[0404] The step of producing a polymerizable composition for an optical material is a step of adding the remainder of the polymerization catalyst to a mixture containing a prepolymer to obtain a polymerizable composition for an optical material containing two or more different monomers for an optical material, a prepolymer, and a polymerization catalyst.
[0405] This can prevent the remaining reactive groups in the mixture including the prepolymer from being polymerized with each other before the mixture including the prepolymer is mixed with the remaining part of the polymerization catalyst.
[0406] Therefore, by performing the step of producing the polymerizable composition for an optical material at an appropriate time, for example, workability when injecting the polymerizable composition for an optical material into a mold can be improved.
[0407] In the step of producing the polymerizable composition for an optical material, when the remaining portion of the polymerization catalyst is added to the mixture containing the prepolymer, the remaining portion of the polymerization catalyst may be mixed at once or in a plurality of divided portions.
[0408] The temperature at the time of mixing the above-mentioned components is not particularly limited, but is preferably 30° C. or lower, and more preferably room temperature (25° C.) or lower.
[0409] The temperature when mixing the components may preferably be lower than 25° C. However, when additives such as an internal mold release agent have poor solubility in the above components, the above components may be heated in advance to dissolve the additives in the above components.
[0410] As a specific aspect of the process of producing the polymerizable composition for an optical material, for example, the following aspects can be mentioned.
[0411] First, an additive (such as an internal mold release agent) is added to a mixture containing a prepolymer to prepare a mixed solution. The mixed solution is stirred at 25° C. for 1 hour to completely dissolve each component, and then degassed to obtain a first mixed solution.
[0412] Separately, the remaining portion of the polymerization catalyst is prepared. If necessary, the remaining portion of the monomer for optical material and the remaining portion of the polymerization catalyst are stirred at 25° C. for 30 minutes to completely dissolve them, thereby obtaining a second mixed solution.
[0413] Then, the first mixed solution and the remaining portion of the polymerization catalyst, or the first mixed solution and the second mixed solution are mixed, stirred, and then degassed to obtain a polymerizable composition for an optical material as a uniform solution.
[0414] <Liquid feeding process>
[0415] The production method B may further include a liquid feeding step of feeding the polymerizable composition for optical material to a casting mold after the step of producing the polymerizable composition for optical material and before the step of curing.
[0416] The liquid feeding step may be a step of feeding the polymerizable composition for optical material to the casting mold while remixing the polymerizable composition for optical material in a static mixer.
[0417] The liquid feeding step may be a step of feeding the polymerizable composition for optical material to the casting mold while remixing the polymerizable composition for optical material with a dynamic mixer.
[0418] This can eliminate uneven distribution of the polymerizable composition for optical material during the period when the polymerizable composition for optical material is conveyed to the mold, and thus can suppress striae in the obtained cured product.
[0419] <Curing process>
[0420] The production method B includes a curing step of curing two or more different optical material monomers in the optical material polymerizable composition to obtain an optical material that is a cured product of the optical material polymerizable composition.
[0421] The specific aspects, preferred aspects, etc. of the curing step in the production method B are the same as the details of the specific aspects, preferred aspects, etc. described in the section of <Curing step> in the above-mentioned production method A.
[0422] <Annealing process>
[0423] The preparation method B may include an annealing step of annealing the cured polymerizable composition for an optical material, if necessary.
[0424] Preferred aspects and the like of the annealing step in the manufacturing method B are the same as those of the annealing step in the manufacturing method A.
[0425] <Other Process>
[0426] For the preparation method B, other steps may be provided as required.
[0427] The specific aspects, preferred aspects, etc. of other steps in Production Method B are the same as those of Production Method A.
[0428] <Applications of optical materials>
[0429] Specific examples, preferred specific examples, and the like of the use of the optical material in Production Method B are the same as those in Production Method A.
[0430] - Second Embodiment -
[0431] 《Methods for producing optical materials》
[0432] The method for producing an optical material according to the second embodiment includes the following steps: a preparation step of preparing a polymerizable composition for an optical material, the polymerizable composition for an optical material comprising a monomer for an optical material containing an episulfide compound and a polymerization catalyst, wherein the content of the polymerization catalyst relative to the total amount of the monomer for an optical material is 0.1150 to 0.2000 parts by mass; and a curing step of curing the polymerizable composition for an optical material by polymerizing the monomer for an optical material in the polymerizable composition for an optical material.
[0433] In the method for producing an optical material according to the second embodiment, specific aspects and preferred aspects of the episulfide compound, the monomer for an optical material, the polymerization catalyst, and the content of the polymerization catalyst are the same as those of the first embodiment described above.
[0434] Specific aspects and preferred aspects of the preparation step are the same as those of the preparation step of the first embodiment described above.
[0435] Specific aspects and preferred aspects in the curing step are the same as those in the curing step of the first embodiment described above.
[0436] In the method for manufacturing an optical material of the second embodiment, the details of the specific examples, preferred specific examples, specific methods, preferred methods, etc. of each component are the same as the details of the specific examples, preferred specific examples, specific methods, preferred methods, etc. of each component in the method for manufacturing an optical material of the first embodiment.
[0437] The second embodiment of the present disclosure includes the following aspects.
[0438] <2-1> A method for producing an optical material, comprising: a preparation step of preparing a polymerizable composition for an optical material, the polymerizable composition for an optical material comprising an optical material monomer containing an episulfide compound and a polymerization catalyst, wherein the content of the polymerization catalyst relative to the total amount of the optical material monomer is 0.1150 to 0.2000 parts by mass; and a curing step of curing the polymerizable composition for an optical material by polymerizing the optical material monomer in the polymerizable composition for an optical material.
[0439] <2-2> The method for producing an optical material according to <2-1>, wherein the preparation step is a step of preparing the polymerizable composition for an optical material by mixing all of the monomers for an optical material in advance and then further mixing the polymerization catalyst.
[0440] <2-3> The method for producing an optical material as described in <2-1> or <2-2>, wherein the preparation step is a step of preliminarily mixing the polymerization catalyst with a part of the monomer for optical material and then further mixing the remaining part of the monomer for optical material to prepare the polymerizable composition for optical material.
[0441] <2-4> The method for producing an optical material according to any one of <2-1> to <2-3>, wherein the curing step is a step of curing the polymerizable composition for optical material by leaving the polymerizable composition for optical material to stand in a closed space.
[0442] <2-5> The method for producing an optical material according to any one of <2-1> to <2-4>, wherein the curing step is a step of curing the polymerizable composition for optical material by leaving the polymerizable composition for optical material to stand without external heating.
[0443] <2-6> The method for producing an optical material according to any one of <2-1> to <2-5>, wherein the curing step is a step of curing the polymerizable composition for optical material by leaving the polymerizable composition for optical material to stand for 6 to 20 hours.
[0444] <2-7> The method for producing an optical material according to any one of <2-1> to <2-6>, wherein the monomer for an optical material further contains at least one of a polythiol compound and an isocyanate compound.
[0445] <2-8> The method for producing an optical material according to any one of <2-1> to <2-7>, wherein the polymerization catalyst includes an amine catalyst.
[0446] <2-9> The method for producing an optical material according to any one of <2-1> to <2-8>, wherein the polymerization catalyst comprises at least one of N,N-dimethylcyclohexylamine and N,N-dicyclohexylmethylamine.
[0447] <2-10> A polymerizable composition for an optical material comprising an optical material monomer containing an episulfide compound and a polymerization catalyst, wherein the content of the polymerization catalyst is 0.1150 to 0.2000 parts by mass based on the total amount of the optical material monomer.
[0448] Example
[0449] The polythiol compound used in this example can be produced by the method described in International Publication No. 2014 / 027665.
[0450] In this example, pKa was determined using the above-mentioned method.
[0451] <Example A>
[0452] Hereinafter, the first and second embodiments of the present disclosure will be specifically described using Example A, but the first and second embodiments are not limited to these Examples.
[0453] The method for measuring the viscosity in Example A is the same as the above-mentioned method.
[0454] The following evaluations were performed on the molded products obtained in the respective Examples and Comparative Examples.
[0455] (Wave tendons)
[0456] The molded product was projected with an ultra-high pressure mercury lamp (light source model OPM-252HEG: manufactured by USHIO Inc.), and the transmitted image was visually observed and evaluated based on the following criteria.
[0457] A: No striae were observed, or striae were not clearly observed. Specifically, striae having a length of 1.0 mm or more were not visually observed within and outside a radius of 15 mm from the center of the molded article.
[0458] B: Although ribs are observed, it is generally acceptable as a product. Specifically, although ribs of 1.0 mm or more in length are visually observed outside the radius of 15 mm from the center of the molded body, ribs of 1.0 mm or more in length are not visually observed within the radius of 15 mm from the center of the molded body, which is generally acceptable as a product.
[0459] C: Streaks were observed, which is unacceptable as a product. Specifically, striae of a length of 1.0 mm or more were visually observed within and outside a radius of 15 mm from the center of the molded article.
[0460] (Mold release)
[0461] The releasability of the molded body when the molded body was released from the molding die was evaluated according to the following criteria.
[0462] A: It peels off even without applying force.
[0463] B: Peeled off when force is applied.
[0464] C: Although it was peeled off when force was applied, there was a possibility that the mold or lens was damaged.
[0465] D: The film could not be peeled off even when force was applied, and no product was obtained.
[0466] [Example 1A to Example 6A]
[0467] 1.1 parts by mass of 2-(5-tert-butyl-2-hydroxyphenyl)benzotriazole (ultraviolet absorber) was added to 100.0 parts by mass of bis(2,3-epithiopropyl)disulfide (epithio compound), and the mixture was stirred at 20°C for 30 minutes to dissolve. 10.0 parts by mass of a mixture containing 4,8-dimercaptomethyl-1,11-dimercapto-3,6,9-trithiaundecane, 4,7-dimercaptomethyl-1,11-dimercapto-3,6,9-trithiaundecane, and 5,7-dimercaptomethyl-1,11-dimercapto-3,6,9-trithiaundecane as main components (polythiol compound) was added to the mixed liquid, and the mixture was stirred at 20°C for 10 minutes. Then, N,N-dimethylcyclohexylamine [DCA, polymerization catalyst, pKa: 10.7] and N,N-dicyclohexylmethylamine [DCH, polymerization catalyst, pKa: 11.0] in an amount as shown in Table 1 were added, and the mixture was stirred at 15° C. for 5 minutes to prepare a uniform solution. The solution was degassed at 400 Pa for 10 minutes to obtain a polymerizable composition for an optical material.
[0468] It should be noted that the content of the polymerization catalyst described in Table 1 means the content of the polymerization catalyst relative to the total amount of the monomer for an optical material (that is, the episulfide compound and the polythiol compound).
[0469] Table 1 shows the viscosity of the polymerizable composition for an optical material, measured using a Brookfield viscometer at 20° C. and 60 rpm, and the thixotropic ratio.
[0470] The polymerizable composition for optical material was filtered through a 1 μm PTFE filter and injected into the cavity of a casting mold at a rate of 10 g / sec.
[0471] As the above-mentioned casting mold, a casting mold having the following dimensions was used.
[0472] S = -6.25D, center thickness is 1.1mm, peripheral thickness is 9mm
[0473] S = -2.25D, center thickness is 1.1mm, peripheral thickness is 4mm
[0474] 4 curves, center thickness 2mm
[0475] 4 bends, center thickness 7mm
[0476] 4 bends, center thickness 10mm
[0477] In addition, the total amount of monomers for optical materials in the polymerizable composition for optical materials is 32 g when S=-6.25D, 16 g when S=-2.25D, 14 g when 4 bends and the center thickness is 2 mm, 50 g when 4 bends and the center thickness is 7 mm, and 65 g when 4 bends and the center thickness is 10 mm.
[0478] The cast was placed in a heat-insulating container at 25°C and allowed to stand for the time described in Table 1 to perform adiabatic polymerization. The solidified molded body was then released from the casting mold and annealed at 110°C for 1 hour to obtain a molded body (lens).
[0479] Table 1 shows the results of striae and mold release properties of the obtained molded product.
[0480] Table 1 shows the amine contents of the obtained molded products (ie, cured products) measured by gas chromatography-mass spectrometry.
[0481] [Comparative Example 1A]
[0482] A polymerizable composition was obtained in the same manner as in Examples 1A to 6A except that the amount of catalyst was as described in Table 1, and injected into the cavity of a casting mold to polymerize, but was not completely cured. Therefore, mold release properties and striae were not evaluated.
[0483] [Comparative Example 2A]
[0484] In Comparative Example 1A, polymerization was performed in the same manner as in Comparative Example 1A except that the casting was cured in a polymerization program (temperature increase program) in which the casting was cured over 42 hours. The cured molded body was demolded and annealed at 110° C. for 1 hour to obtain a molded body.
[0485] Table 1 shows the results of striae and mold release properties of the obtained molded product.
[0486] [Table 1]
[0487]
[0488] As described above, in Examples 1A to 6A in which the step of preparing a polymerizable composition for an optical material including an episulfide compound-containing monomer for an optical material and a polymerization catalyst, wherein the content of the polymerization catalyst is 0.1150 to 0.2000 parts by mass based on the total amount of the monomer for an optical material, a molded product with good releasability and striae can be obtained in a short time of 10 to 18 hours.
[0489] Among them, in Examples 1A to 5A in which the content of the polymerization catalyst was 0.1200 parts by mass or more based on the total amount of the monomers for an optical material, a molded product having good releasability and striae could be obtained in a shorter time.
[0490] On the other hand, in Comparative Example 1A in which the content of the polymerization catalyst relative to the total amount of the optical material monomers was less than 0.1150 parts by mass and the optical material polymerizable composition was left to stand in a heat-insulating environment to perform heat-insulating polymerization, the mold releasability was poor and a good molded product could not be obtained.
[0491] In addition, for Comparative Example 2A in which the content of the above-mentioned polymerization catalyst relative to the total amount of monomers for optical materials is less than 0.1150 parts by mass, although a molded body with good demolding properties and ribs can be obtained, heating using a polymerization oven is required, and the polymerization time is also longer than that of the embodiment.
[0492] The graph showing the relationship between polymerization time and temperature when the total mass of the optical material monomers in the optical material polymerizable composition is 30 g and a molded body is produced using the optical material polymerizable composition of Example 1A, Example 2A to Example 4A, Example 5A and Example 6A is shown in FIG. Figure 1 .
[0493] <Example B>
[0494] Hereinafter, the production method B of the first embodiment will be specifically described with reference to Example B, but the production method B of the first embodiment is not limited to these Examples.
[0495] The method for measuring the viscosity in Example B is the same as the above-mentioned method.
[0496] In Example B, the amine content in the cured product was measured by the above-mentioned method.
[0497] The following evaluations were performed on the molded products obtained in the respective Examples and Comparative Examples.
[0498] (Wave tendons)
[0499] The molded product was projected with an ultra-high pressure mercury lamp (light source model OPM-252HEG: manufactured by USHIO Inc.), and the transmitted image was visually observed and evaluated based on the following criteria.
[0500] A: No striae were observed. Specifically, striae having a length of 1.0 mm or more were not observed by visual inspection within and outside a radius of 15 mm from the center of the molded article.
[0501] B: Although ribs are observed, it is generally acceptable as a product. Specifically, although ribs of 1.0 mm or more in length are visually observed outside the radius of 15 mm from the center of the molded body, ribs of 1.0 mm or more in length are not visually observed within the radius of 15 mm from the center of the molded body, which is generally acceptable as a product.
[0502] C: Streaks were observed, which is unacceptable as a product. Specifically, striae of a length of 1.0 mm or more were visually observed within and outside a radius of 15 mm from the center of the molded article.
[0503] (Mold release)
[0504] The releasability of the molded body when the molded body was released from the molding die was evaluated according to the following criteria.
[0505] A: It peels off even without applying force.
[0506] B: Peeled off when force is applied.
[0507] C: Although it was peeled off when force was applied, there was a possibility that the mold or lens was damaged.
[0508] D: The film could not be peeled off even when force was applied, and no product was obtained.
[0509] [Example 1B]
[0510] 1.1 parts by mass of 2-(5-tert-butyl-2-hydroxyphenyl)benzotriazole (ultraviolet absorber) was added to 100.0 parts by mass of bis(2,3-epithiopropyl)disulfide (epithio compound), and the mixture was stirred at 20°C for 30 minutes to dissolve. 10.0 parts by mass of a mixture containing 4,8-dimercaptomethyl-1,11-dimercapto-3,6,9-trithiaundecane, 4,7-dimercaptomethyl-1,11-dimercapto-3,6,9-trithiaundecane, and 5,7-dimercaptomethyl-1,11-dimercapto-3,6,9-trithiaundecane as main components (polythiol compound) was added to the mixed solution, and the mixture was stirred at 20°C for 10 minutes to prepare a uniform solution.
[0511] To the obtained uniform solution, 0.02 parts by mass of N,N-dimethylcyclohexylamine [DCA, polymerization catalyst] was further added, and the mixture was stirred at 20° C. for 6 hours. The monomer for optical material was polymerized while adjusting the viscosity, and the solution was degassed at 400 Pa for 10 minutes to obtain a mixed solution containing a prepolymer. The viscosity of the mixture containing the prepolymer is shown in Table 2.
[0512] To the obtained mixed solution, 0.1 parts by mass of N,N-dicyclohexylmethylamine [DCH, polymerization catalyst] was added and mixed at 20° C. to obtain a polymerizable composition for an optical material.
[0513] Table 2 shows the value obtained by subtracting the refractive index B of the prepolymer raw material composition (which is a composition before forming a prepolymer and contains two or more different monomers for optical materials and a polymerization catalyst) from the refractive index A of the polymerizable prepolymer composition for optical materials (also referred to as "refractive index A-refractive index B").
[0514] Table 2 shows the viscosity of the polymerizable composition for an optical material, measured using a Brookfield viscometer at 20° C. and 60 rpm, and the thixotropic ratio.
[0515] The obtained polymerizable composition for optical material is transferred to a casting mold (ie, a casting die) while being remixed in a static mixer.
[0516] The viscosity of the polymerizable composition for an optical material when transferred to the mold and cast (also referred to as casting viscosity) was adjusted to the value shown in Table 2.
[0517] The polymerizable composition for optical material was filtered through a 1 μm PTFE filter and injected into the cavity of a casting mold at a rate of 10 g / sec.
[0518] As the above-mentioned casting mold, a casting mold having the following dimensions was used.
[0519] S = -6.25D, center thickness is 1.1mm, peripheral thickness is 9mm
[0520] ·4 bends, center thickness 2mm
[0521] 4 bends, center thickness 7mm
[0522] The cast was placed in a heat-insulated container at 25° C. and allowed to stand for 5 hours to perform heat-insulating polymerization. Thereafter, the solidified molded body was released from the casting mold and further annealed at 110° C. for 1 hour to obtain a molded body (lens).
[0523] [Example 2B]
[0524] A molded body (lens) was obtained by the same method as in Example 1B except that the content of DCA was changed to 0.03 parts by mass. The cured molded body was demolded and further annealed at 110° C. for 1 hour to obtain a molded body.
[0525] Table 1 shows the results of striae and mold release properties of the obtained molded product.
[0526] [Table 2]
[0527]
[0528] As shown in Table 2, the embodiment using the method for producing an optical material is excellent in the evaluation of striae, and thus striae can be suppressed, wherein the method for producing an optical material comprises the following steps: a preparation step of preparing two or more different monomers for optical materials and a polymerization catalyst in an amount of 0.1150 to 0.2000 parts by mass relative to the total amount of the two or more different monomers for optical materials; and a prepolymerization step of mixing at least a part of the two or more different monomers for optical materials and at least a part of the polymerization catalyst, polymerizing at least a part of the two or more different monomers for optical materials, and obtaining a prepolymer, thereby obtaining a mixture containing the prepolymer, wherein at least one of the two or more different monomers for optical materials is an episulfide compound. In addition, the polymerization time is 5 hours, and thus the production time of the optical material can be shortened.
[0529] The entire disclosure of Japanese Patent Application No. 2020-041402 filed on March 10, 2020 and Japanese Patent Application No. 2020-194660 filed on November 24, 2020 are incorporated into this specification by reference.
[0530] All documents, patent applications, and technical standards described in this specification are incorporated into this specification by reference to the same extent as if each document, patent application, and technical standard was specifically and individually described.
Claims
1. A cured product, which is a cured product of two or more different monomers for optical materials, wherein the two or more different monomers for optical materials include an episulfide compound and a polythiol compound, wherein there are no ribs having a length of 1.0 mm or more within a radius of 15 mm from the center of the cured product, and the content of amine measured by gas chromatography-mass spectrometry is 0.01% by mass or more and 0.20% by mass or less, wherein the amine includes a compound represented by the following general formula (3) and / or a compound represented by the following general formula (2), In the general formula (3), R2, R3 and R4 each independently represent a linear alkyl group having 1 to 20 carbon atoms, a branched alkyl group having 3 to 20 carbon atoms, a cycloalkyl group having 3 to 20 carbon atoms, an allyl group, or a hydrocarbon group containing a hydroxyl group, In the general formula (2), R1 represents a straight-chain alkyl group having 1 to 20 carbon atoms, a branched alkyl group having 3 to 20 carbon atoms, a cycloalkyl group having 3 to 20 carbon atoms, or a halogen atom, and multiple R1s may be the same or different; Q represents a carbon atom or a nitrogen atom; and m represents an integer from 0 to 5.
2. The cured product according to claim 1, wherein The amine includes a compound represented by the following general formula (3): In the general formula (3), R2, R3 and R4 each independently represent a linear alkyl group having 1 to 20 carbon atoms, a branched alkyl group having 3 to 20 carbon atoms, or a cycloalkyl group having 3 to 20 carbon atoms.
3. The cured product according to claim 1 or 2, wherein The amine includes at least one selected from the group consisting of triethylenediamine, N,N-dimethylcyclohexylamine, N,N-dicyclohexylmethylamine, N,N-dimethylethanolamine, triethylamine, N-ethylmorpholine, 2-methylpyrazine, pyridine, α-methylpyridine, β-methylpyridine, γ-methylpyridine, 2,6-lutidine, 3,5-lutidine, 2,4,6-trimethylpyridine, 3-chloropyridine, N,N-diethylaniline, N,N-dimethylaniline, hexamethylenetetramine, quinoline, isoquinoline, N,N-dimethyl-p-toluidine, N,N-dimethylpiperazine, quinaldine, 4-methylmorpholine, triallylamine, trioctylamine, 1,2-dimethylimidazole, and 1-benzyl-2-methylimidazole.
4. The cured product according to claim 1 or 2, wherein The episulfide compound includes at least one selected from the group consisting of bis(2,3-epithiopropyl)sulfide, bis(2,3-epithiopropyl)disulfide, bis(1,2-epithioethyl)sulfide, bis(1,2-epithioethyl)disulfide, and bis(2,3-epithiopropylthio)methane.
5. The cured product according to claim 1 or 2, wherein The polythiol compound comprises 4-mercaptomethyl-1,8-dimercapto-3,6-dithia-octane, 5,7-dimercaptomethyl-1,11-dimercapto-3,6,9-trithia-undecane, 4,7-dimercaptomethyl-1,11-dimercapto-3,6,9-trithia-undecane, 4,8-dimercaptomethyl-1,11-dimercapto-3,6,9-trithia-undecane, pentaerythritol tetra(3- At least one of the group consisting of bis(mercaptopropionate), bis(mercaptoethyl) sulfide, pentaerythritol tetrakis(2-mercaptoacetate), 2,5-bis(mercaptomethyl)-1,4-dithiane, 1,1,3,3-tetrakis(mercaptomethylthio)propane, 4,6-bis(mercaptomethylthio)-1,3-dithiane, and 2-(2,2-bis(mercaptomethylthio)ethyl)-1,3-dithiane.
Citation Information
Patent Citations
Binding machine
JP2020041402A
LED lighting device
JP2020194660A
Production method for polythiol compound, polymerizable composition for optical material and use therefor
WO2014027427A1
Optical material, composition for use therein, and use thereof
WO2014133111A1
Polymerizable composition for optical material, and optical material
WO2015137401A1